A computer-aided detection system in the everyday setting of diagnostic, screening and surveillance colonoscopy: an international, randomized trial - Maas, Michiel Hendrik Joël; Rath, Timo; Spada, Cristiano; Soons, Elsa; Forbes, Nauzer; Kashin, Sergey; Cesaro, Paola; Eickhoff, Axel; Vanbiervliet, Geoffroy; Salvi, Daniele; Belletrutti, Paul James; Siersema, Peter D. (Endoscopy, 2024)
Background and study aim: Computer-aided detection (CADe) has been developed to improve detection during colonoscopy. After initial reports of high efficacy, there has been an increasing recognition of variability in the effectiveness of CADe systems. The aim of this study was to evaluate a CADe system (PENTAX Medical, Tokyo, Japan) in a varied colonoscopy population. Patients and methods: A multicenter, randomized trial was conducted at 7 hospitals (both university and non-university) in Europe and Canada. Participants referred for diagnostic, non-iFOBT screening, or surveillance colonoscopy were randomized (1:1) to undergo CADe-assisted or conventional colonoscopy (CC) by experienced endoscopists. Participants with insufficient bowel preparation were excluded from the analysis. Primary outcome was adenoma detection rate (ADR). Secondary outcomes included adenomas per colonoscopy (APC) and sessile serrated lesions per colonoscopy (SSLPC). Results: In total, 581 participants were enrolled, of which 497 were included in the final analysis: 250 in the CADe-arm and 247 in the CC-arm. Surveillance was the indication in 202/497 (40.6%) colonoscopies, diagnostic in 199/497 (40.0%), and non-iFOBT screening in 96/497 (19.3%). Overall, ADR (38.4% vs. 37.7%; p=0.43) and APC (0.66 vs. 0.66; p=0.97) were similar between CADe and CC. SSLPC was increased (0.30 vs. 0.19; p=0.049) in the CADe-arm vs. CC. Conclusions: In this study conducted by experienced endoscopists, CADe did not result in a statistically significant increase in ADR. However, the ADR of our control group substantially surpassed our sample size assumptions, increasing the risk of an underpowered trial. (Trialsearch.who.int:NL9135).
CRIS-Team Scopus Importer:2024-05-31

Advanced Endoscopic Imaging in Colonic Neoplasia - Rath, Timo; Morgenstern, Nadine; Vitali, Francesco; Atreya, Raja; Neurath, Markus (Visceral Medicine, 2020)
Background: Endoscopic imaging is a rapidly evolving field with a constant influx of new concepts and technologies. Since the introduction of video endoscopy and subsequently high-definition imaging as the first revolutions in gastrointestinal endoscopy, several technologies of virtual chromoendoscopy have been developed and brought to the market in the past decade, which have shaped and revolutionized for a second time our approach to endoscopic imaging. In parallel to these developments, microscopic imaging technologies, such as endomicroscopy and endocytoscopy, allow us to examine single cells within the mucosa in real time, thereby enabling histological diagnoses during ongoing endoscopy. Summary: In this review, we provide an overview on the technical background of different technologies of advanced endoscopic imaging, and then review and discuss their role and applications for the diagnosis and management of colorectal neoplasms as well as limitations and challenges that exist despite all technological improvements. Key Messages: Technologies of advanced endoscopic imaging have profound impact not only on our imaging capabilities, they are also about to fundamentally change our approach to managing lesions in the gastrointestinal tract: Not every lesion found during colonoscopy has to be excised or sent for histopathologic evaluation. However, before this becomes widespread reality, major obstacles such as patient acceptance, adoption by less trained endoscopists, and also legal aspects need to carefully addressed. The development of computer-aided diagnosis and artificial intelligence algorithms hold the potential to overcome the obstacles associated with the concept of optical biopsy and will most likely fundamentally facilitate, shape, and change decision making in the management of colorectal lesions.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Colorectal cancer; Colorectal polyps; Endocytoscopy; Endomicroscopy; Endoscopy

A new simplified histology artificial intelligence system for accurate assessment of remission in Ulcerative Colitis - Villanacci, V.; Parigi, T. L.; Del Amor, R.; Esbri, P. Mesguer; Gui, X.; Bazarova, A.; Bhandari, P.; Bisschops, R.; Danese, S.; De Hertogh, G.; Ferraz, J. G.; Goetz, M.; et al. (JOURNAL OF CROHNS & COLITIS, 2022)
CRIS-Team WoS Importer:2022-05-13

(untitled)
Background & Aims: Endoscopic and histologic remission are important goals in the treatment of ulcerative colitis (UC). We investigated the correlation of the recently developed Paddington International Virtual ChromoendoScopy ScOre (PICaSSO) and other established endoscopic scores against multiple histological indices and prospectively assessed outcomes. Methods: In this prospective multicenter international study, inflammatory activity was assessed with high-definition and virtual chromoendoscopy in the rectum and sigmoid using the Mayo Endoscopic Score (MES), UC Endoscopic Index of Severity (UCEIS), and PICaSSO. Targeted biopsies were taken for assessment using Robarts Histological Index (RHI), Nancy Histological index (NHI), ECAP (Extent, Chronicity, Activity, Plus score), Geboes, and Villanacci. Follow-up data were obtained at 6 and 12 months after colonoscopy. Results: A total of 307 patients were recruited. There was strong correlation between PICaSSO and histology scores, significantly superior to correlation coefficients of MES and UCEIS with histology scores. A PICaSSO score of ≤3 detected histologic remission by RHI (≤3 + absence of neutrophils) with area under the receiver operating characteristic curve (AUROC) 0.90 (95% confidence interval [CI] 0.86–0.94) and NHI (≤1) AUROC 0.82 (95% CI 0.77–0.87). The interobserver agreement for PICaSSO was 0.88 (95% CI 0.83–0.92). At 6- and 12-months follow-up, PICaSSO score ≤3 predicted better outcomes than PICaSSO >3 (hazard ratio [HR] 0.19 [0.11–0.33] and 0.22 [0.13–0.34], respectively),

Artificial Intelligence Enabled Histological Prediction of Remission or Activity and Clinical Outcomes in Ulcerative Colitis - Iacucci, Marietta; Parigi, Tommaso Lorenzo; Del Amor, Rocio; Meseguer, Pablo; Mandelli, Giulio; Bozzola, Anna; Bazarova, Alina; Bhandari, Pradeep; Bisschops, Raf; Danese, Silvio; De Hertogh, Gert; Ferraz, Jose G.; et al. (Gastroenterology, 2023)
Background & Aims: Microscopic inflammation has significant prognostic value in ulcerative colitis (UC); however, its assessment is complex with high interobserver variability. We aimed to develop and validate an artificial intelligence (AI) computer-aided diagnosis system to evaluate UC biopsies and predict prognosis. Methods: A total of 535 digitalized biopsies (273 patients) were graded according to the PICaSSO Histologic Remission Index (PHRI), Robarts, and Nancy Histological Index. A convolutional neural network classifier was trained to distinguish remission from activity on a subset of 118 biopsies, calibrated on 42 and tested on 375. The model was additionally tested to predict the corresponding endoscopic assessment and occurrence of flares at 12 months. The system output was compared with human assessment. Diagnostic performance was reported as sensitivity, specificity, prognostic prediction through Kaplan-Meier, and hazard ratios of flares between active and remission groups. We externally validated the model in 154 biopsies (58 patients) with similar characteristics but more histologically active patients. Results: The system distinguished histological activity/remission with sensitivity and specificity of 89% and 85% (PHRI), 94% and 76% (Robarts Histological Index), and 89% and 79% (Nancy Histological Index). The model predicted the corresponding endoscopic remission/activity with 79% and 82% accuracy for UC endoscopic index of severity and Paddington International virtual ChromoendoScopy ScOre, respectively. The hazard ratio for disease flare-up between histological activity/remission groups according to pathologist-assessed PHRI was 3.56, and 4.64 for AI-assessed PHRI. Both histology and outcome prediction were confirmed in the external validation cohort. Conclusion: We developed and validated an AI model that distinguishes histologic remission/activity in biopsies of UC and predicts flare-ups. This can expedite, standardize, and enhance histologic assessment in practice and trials.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Computer-aided Diagnosis; Convolutional Neural Network; PICaSSO Histologic Remission Index; Robarts Histopathology Index; Ulcerative Colitis

A spotlight on intestinal permeability and inflammatory bowel diseases - Rath, Timo; Atreya, Raja; Neurath, Markus (Expert Review of Gastroenterology and Hepatology, 2023)
Introduction: The intestinal barrier is a multi-faced structure lining the surface of the intestinal mucosa of the GI tract. To exert its main functions as a physical and immunological defense barrier, several components of the intestinal barrier act in a concerted and cooperative manner. Areas covered: Herein, we first introduce to the basic organization of the intestinal barrier and then summarize different methods to assess barrier function in and ex vivo. Finally, we provide an in-depth overview of the relevance of intestinal barrier dysfunction in inflammatory bowel diseases. Expert opinion: In parallel to a more fundamental understanding of the intestinal barrier as a key component for intestinal integrity is the notion that intestinal barrier defects are associated with a variety of diseases such as inflammatory bowel diseases. Recent research has fueled and perpetuated the concept that barrier defects are critical components of disease development, disease behavior, and potentially also an area of therapeutic intervention in IBD patients. Although being far away from standard, new technologies can be used to easily assess barrier healing in IBD and to derive clinical consequences from these findings such as more accurate forecasting of future disease behavior or the identification of novel therapeutic targets.
CRIS-Team Scopus Importer:2023-11-24
Keywords: confocal laser endomicroscopy; Crohn’s disease; inflammatory bowel diseases; Intestinal barrier; intestinal permeability; leaky gut; ulcerative colitis

Autologous regulatory T-cell transfer in refractory ulcerative colitis with concomitant primary sclerosing cholangitis - Voskens, Caroline; Stoica, Diane; Rosenberg, Marita; Vitali, Francesco; Zundler, Sebastian; Ganslmayer, Marion; Knott, Heike; Wiesinger, Manuel; Wunder, Jutta; Kummer, Mirko; Siegmund, Britta; Schnoy, Elisabeth; et al. (Gut, 2022)
Objective Ulcerative colitis (UC) is a chronic, debilitating immune-mediated disease driven by disturbed mucosal homeostasis, with an excess of intestinal effector T cells and an insufficient expansion of mucosal regulatory T cells (Tregs). We here report on the successful adoptive transfer of autologous, ex vivo expanded Tregs in a patient with refractory UC and associated primary sclerosing cholangitis (PSC), for which effective therapy is currently not available.
CRIS-Team WoS Importer:2022-04-29

A virtual chromoendoscopy artificial intelligence system to detect endoscopic and histologic activity/remission and predict clinical outcomes in ulcerative colitis - Iacucci, Marietta; Cannatelli, Rosanna; Parigi, Tommaso L.; Nardone, Olga M.; Tontini, Gian Eugenio; Labarile, Nunzia; Buda, Andrea; Rimondi, Alessandro; Bazarova, Alina; Bisschops, Raf; Del Amor, Rocio; Meseguer, Pablo; et al. (Endoscopy, 2022)
Background Endoscopic and histological remission (ER, HR) are therapeutic targets in ulcerative colitis (UC). Virtual chromoendoscopy (VCE) improves endoscopic assessment and the prediction of histology; however, interobserver variability limits standardized endoscopic assessment. We aimed to develop an artificial intelligence (AI) tool to distinguish ER/activity, and predict histology and risk of flare from white-light endoscopy (WLE) and VCE videos. Methods 1090 endoscopic videos (67 280 frames) from 283 patients were used to develop a convolutional neural network (CNN). UC endoscopic activity was graded by experts using the Ulcerative Colitis Endoscopic Index of Severity (UCEIS) and Paddington International virtual ChromoendoScopy ScOre (PICaSSO). The CNN was trained to distinguish ER/activity on endoscopy videos, and retrained to predict HR/activity, defined according to multiple indices, and predict outcome; CNN and human agreement was measured. Results The AI system detected ER (UCEIS = 1) in WLE videos with 72% sensitivity, 87% specificity, and an area under the receiver operating characteristic curve (AUROC) of 0.85; for detection of ER in VCE videos (PICaSSO = 3), the sensitivity was 79 %, specificity 95%, and the AUROC 0.94. The prediction of HR was similar between WLE and VCE videos (accuracies ranging from 80% to 85%). The model s stratification of risk of flare was similar to that of physician-assessed endoscopy scores. Conclusions Our system accurately distinguished ER/activity and predicted HR and clinical outcome from colonoscopy videos. This is the first computer model developed to detect inflammation/healing on VCE using the PICaSSO and the first computer tool to provide endoscopic, histologic, and clinical assessment.
CRIS-Team Scopus Importer:2024-12-16

Barrett's Esophagus: Today's Mistakes and Tomorrow's Wisdom - Pouw, Roos E.; Pech, Oliver; Haidry, Rehan; Bisschops, Raf; Rath, Timo; Gisbertz, Suzanne (Visceral Medicine, 2022)
CRIS-Team WoS Importer:2022-06-03

Be precise, be reproducible! the emerging role of artificial intelligence in inflammatory bowel disease endoscopy - Tontini, Gian Eugenio; Rath, Timo (Journal of Crohns & Colitis, 2025)
CRIS-Team Scopus Importer:2025-05-23

Chronic Inflammatory Bowel Disease - Recent aspects Chronisch entzündliche Darmerkrankungen - Aktuelle Aspekte - Vieth, M.; Rath, Timo; Bästlein, E. C.; Neumann, Helmut (Endoskopie heute, 2015)
Inflammation plays a huge role in carcinogenesis in inflammatory bowel disease (IBD). Due to the close relation of extent and degree of inflammation in colitis-associated carcinomas modern treatment strategies seek for minimizing mucosal inflammation or even mucosal healing. Gastrointestinal endoscopy and histopathology play a pivotal role not only for diagnostics but also for endoscopic removal. Clear cut definitions of criteria are mandatory to ensure a high quality setup. At our institution more than 90% of all carcinomas in IBD develop in ulcerative colitis. Therefore, we will focus on ulcerative colitis and ulcerative colitis-associated carcinomas in the present manuscript. It is known that aside from specialized centers that instead of performing proctocolectomies partial colectomies are carried out in case of colitis-associated carcinomas. Our retrospective data show that partial colectomies bear a higher risk for relapses on base of lymph node metastases and metachronous lesions as well. Survival rates of partial and complete colectomies are comparable but proctocolectomies are still the therapy of choice for carcinomas in ulcerative colitis.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Crohn's disease; histology carcinoma; treatment; ulcerative colitis

Comparison of Hemospray® and Endoclot™ for the treatment of gastrointestinal bleeding - Vitali, Francesco; Naegel, Andreas; Atreya, Raja; Zopf, Steffen; Neufert, Clemens; Neurath, Markus; Rath, Timo; Siebler, Jürgen (World Journal of Gastroenterology, 2019)
BACKGROUND Gastrointestinal (GI) bleeding is a common indication for endoscopy. For refractory cases, hemostatic powders (HP) represent “touch-free” agents. AIM To analyze short term (ST-within 72 h-) and long-term (LT-within 30 d-) success for achieving hemostasis with HP and to directly compare the two agents Hemospray (HS) and Endoclot (EC). METHODS HP was applied in 154 consecutive patients (mean age 67 years) with GI bleeding. Patients were followed up for 1 mo (mean follow-up: 3.2 mo). RESULTS Majority of applications were in upper GI tract (89%) with following bleeding sources: peptic ulcer disease (35%), esophageal varices (7%), tumor bleeding (11.7%), reflux esophagitis (8.7%), diffuse bleeding and erosions (15.3%). Overall ST success was achieved in 125 patients (81%) and LT success in 81 patients (67%). Re-bleeding occurred in 27% of all patients. In 72 patients (47%), HP was applied as a salvage hemostatic therapy, here ST and LT success were 81% and 64%, with re-bleeding in 32%. As a primary hemostatic therapy, ST and LT success were 82% and 69%, with re-bleeding occurring in 22%. HS was more frequently applied for upper GI bleeding (P = 0.04) CONCLUSION Both HP allow for effective hemostasis with no differences in ST, LT success and re-bleeding.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Endoclot; Gastrointestinal bleeding; Haemostasis; Hemospray; Hemostatic powder

Comparison of Hemospray (R) and Endoclot (TM) for the treatment of gastrointestinal bleeding - Vitali, Francesco; Naegel, Andreas; Atreya, Raja; Zopf, Steffen; Neufert, Clemens; Neurath, Markus; Rath, Timo; Siebler, Jürgen (World Journal of Gastroenterology, 2019)
BACKGROUND
CRIS-Team WoS Importer:2019-04-16

Computer-aided detection of colorectal polyps using a newly generated deep convolutional neural network: from development to first clinical experience - Pfeifer, Lukas; Neufert, Clemens; Leppkes, Moritz; Waldner, Maximilian; Hafner, Michael; Beyer, Albert; Hoffman, Arthur; Siersema, Peter D.; Neurath, Markus; Rath, Timo (European Journal of Gastroenterology & Hepatology, 2021)
Aim The use of artificial intelligence represents an objective approach to increase endoscopist's adenoma detection rate (ADR) and limit interoperator variability. In this study, we evaluated a newly developed deep convolutional neural network (DCNN) for automated detection of colorectal polyps ex vivo as well as in a first in-human trial.
CRIS-Team WoS Importer:2022-03-18

CONFOCAL LASER ENDOMICROSCOPY CAN PREDICT MAJOR CLINICAL EVENTS WITH VERY HIGH SENSITIVITY IN PATIENTS WITH INFLAMMATORY BOWEL DISEASES - Klenske, Entcho; Atreya, Raja; Zundler, Sebastian; Fischer, Sven Moritz; Neurath, Markus; Rath, Timo (GASTROINTESTINAL ENDOSCOPY, 2019)
CRIS-Team WoS Importer:2019-06-21

Constrained multiple instance learning for ulcerative colitis prediction using histological images - Del Amor, Rocio; Meseguer, Pablo; Parigi, Tommaso Lorenzo; Villanacci, Vincenzo; Colomer, Adrian; Launet, Laetitia; Bazarova, Alina; Tontini, Gian Eugenio; Bisschops, Raf; De Hertogh, Gert; Ferraz, Jose G.; Goetz, Martin; et al. (Computer Methods and Programs in Biomedicine, 2022)
Background and Objective: Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) affecting the colon and the rectum characterized by a remitting-relapsing course. To detect mucosal inflammation as-sociated with UC, histology is considered the most stringent criteria. In turn, histologic remission (HR) correlates with improved clinical outcomes and has been recently recognized as a desirable treatment target. The leading biomarker for assessing histologic remission is the presence or absence of neutrophils. Therefore, the finding of this cell in specific colon structures indicates that the patient has UC activity. However, no previous studies based on deep learning have been developed to identify UC based on neu-trophils detection using whole-slide images (WSI). Methods: The methodological core of this work is a novel multiple instance learning (MIL) framework with location constraints able to determine the presence of UC activity using WSI. In particular, we put forward an effective way to introduce constraints about positive instances to effectively explore additional weakly supervised information that is easy to obtain and enjoy a significant boost to the learning process. In addition, we propose a new weighted embedding to enlarge the relevance of the positive instances. Results: Extensive experiments on a multi-center dataset of colon and rectum WSIs, PICASSO-MIL, demon-strate that using the location information we can improve considerably the results at WSI-level. In com-parison with prior MIL settings, our method allows for 10% improvements in bag-level accuracy. Conclusion : Our model, which introduces a new form of constraints, surpass the results achieved from current state-of-the-art methods that focus on the MIL paradigm. Our method can be applied to other histological concerns where the morphological features determining a positive WSI are tiny and similar to others in the image. (c) 2022 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2022-09-02

Cross-sectional imaging of intestinal barrier dysfunction by confocal laser endomicroscopy can identify patients with food allergy in vivo with high sensitivity - Rath, Timo; Dieterich, Walburga; Kätscher-Murad, Christiane; Neurath, Markus; Zopf, Yurdagül (Scientific Reports, 2021)
Food allergy (FA) affects approximately 3 to 4% of the adult population in westernized countries. Suspected FA is even more prevalent and requires extensive diagnostic work-up. Within this study, we evaluated whether assessment of the integrity of the epithelial barrier by confocal laser endomicroscopy (CLE) during colonoscopy can be used as a screening tool to identify patients with FA. 60 patients with suspected FA were prospectively included. Serology with total and food-specific IgE, anti-tissue transglutaminase, skin prick testing, food intolerance tests, food intake registration and assessment of clinical complaints were performed. During colonocopy, standardized CLE was performed in the terminal ileum and at two colorectal sites. Analysis of CLE images included functional (i.e. presence of epithelial barrier dysfunction) and quantitative parameters of intestinal architecture. 27 of 60 patients (45%) were diagnosed with FA. Barrier dysfunction was analyzed on 65.837 ileal and on 93.251 colonic images. 96% of patients with FA exhibited functional and structural barrier defects while barrier dysfunction was found in only 33% of patients without FA (p < 0.0001). Visualizing barrier dysfunction with CLE for in vivo diagnosis of FA had a sensitivity and specificity of 96% and 67%, respectively, with a positive and negative prediction of 70% and 96%, respectively. Parameters intrinsic to the crypt architecture including crypt diameter, intercrypt distance, crypt lumen diameter and colonic vasculature were not different between patients with and without FA. CLE-based imaging of the intestinal barrier during colonoscopy might help in stratifying patients with suspected FA for further diagnostic work-up.
CRIS-Team Scopus Importer:2021-06-25

Current and Emerging Targeted Therapies for Ulcerative Colitis. - Pietschner, Robert; Rath, Timo; Neurath, Markus; Atreya, Raja (Visceral Medicine, 2023)
BACKGROUND: Ulcerative colitis is one of the main entities of inflammatory bowel diseases. The clinical course of this immune-mediated disorder is marked by unpredictable exacerbations and asymptomatic remission, causing lifelong morbidity. Optimized anti-inflammatory treatment is a prerequisite to not only restore the quality of life of the affected patients but also halt progressive bowel damage and reduce the risk for colitis-associated neoplasia. Advances in understanding the underlying immunopathogenesis of ulcerative colitis have led to the advent of targeted therapies that selectively inhibit crucial molecular structures or signaling pathways that perpetuate the inflammatory reaction. SUMMARY: We will delineate the mode of action and summarize efficacy and safety data of current and emerging targeted therapies in ulcerative colitis, which encompasses representatives of the drug classes of antibodies, small molecules, and oligonucleotides. These substances have already been approved for induction and maintenance treatment or are being tested in late-stage clinical trials in moderately-to-severely active ulcerative colitis patients. These advanced therapies have enabled us to define and achieve novel therapeutic outcomes, such as clinical and endoscopic remission, histological remission, mucosal healing, and recently, also barrier healing as an emerging outcome measure. KEY MESSAGES: Established and emerging targeted therapies and monitoring modalities broaden our therapeutic armamentarium and have enabled us to define novel therapeutic outcomes that have the potential to modify the individual disease course of patients with ulcerative colitis.
EVALuna2:550705

Current Endoscopic Resection Techniques for Gastrointestinal Lesions: Endoscopic Mucosal Resection, Submucosal Dissection, and Full-Thickness Resection - Hoffman, Arthur; Atreya, Raja; Rath, Timo; Neurath, Markus (Visceral Medicine, 2021)
Background: Endoscopic resection of dysplastic lesions in early stages of cancer reduces mortality rates and is recommended by many national guidelines throughout the world. Snare polypectomy and endoscopic mucosal resection (EMR) are established techniques of polyp removal. The advantages of these methods are their relatively short procedure times and acceptable complication rates. The latter include delayed bleeding in 0.9% and a perforation risk of 0.4-1.3%, depending on the size and location of the resected lesion. EMR is a recent modification of endoscopic resection. A limited number of studies suggest that larger lesions can be removed en bloc with low complication rates and short procedure times. Novel techniques such as endoscopic submucosal dissection (ESD) are used to enhance en bloc resection rates for larger, flat, or sessile lesions. Endoscopic full-thickness resection (EFTR) is employed for non-lifting lesions or those not easily amenable to resection. Procedures such as ESD or EFTR are emerging standards for lesions inaccessible to EMR techniques. Summary: Endoscopic treatment is now regarded as first-line therapy for benign lesions. Key Message: Endoscopic resection of dysplastic lesions or early stages of cancer is recommended. A plethora of different techniques can be used dependent on the lesions.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Complication rates; Early cancer; Endoscopic resection; Resection techniques

Development and Initial Validation of a New Endoscopic Training Model for Advanced Endoscopic Procedures - The HEAT International Endoscopy Study - Neumann, Helmut; Buder, Thomas; Loeffler, Silke; Rath, Timo; Naegel, Andreas; Neuhuber, Winfried (2016)
EVALuna2:184251

Development and validation of the SIMPLE endoscopic classification of diminutive and small colorectal polyps - Iacucci, Marietta; Trovato, Cristina; Daperno, Marco; Akinola, Oluseyi; Greenwald, David; Gross, Seth A.; Hoffman, Arthur; Lee, Jeffrey; Lethebe, Brendan C.; Lowerison, Mark; Nayor, Jennifer; Neumann, Helmut; et al. (Endoscopy, 2018)
BACKGROUND: Prediction of histology of small polyps facilitates colonoscopic treatment. The aims of this study were: 1) to develop a simplified polyp classification, 2) to evaluate its performance in predicting polyp histology, and 3) to evaluate the reproducibility of the classification by trainees using multiplatform endoscopic systems. METHODS: In phase 1, a new simplified endoscopic classification for polyps - Simplified Identification Method for Polyp Labeling during Endoscopy (SIMPLE) - was created, using the new I-SCAN OE system (Pentax, Tokyo, Japan), by eight international experts. In phase 2, the accuracy, level of confidence, and interobserver agreement to predict polyp histology before and after training, and univariable/multivariable analysis of the endoscopic features, were performed. In phase 3, the reproducibility of SIMPLE by trainees using different endoscopy platforms was evaluated. RESULTS: Using the SIMPLE classification, the accuracy of experts in predicting polyps was 83 % (95 % confidence interval [CI] 77 % - 88 %) before and 94 % (95 %CI 89 % - 97 %) after training (P = 0.002). The sensitivity, specificity, positive predictive value, and negative predictive value after training were 97 %, 88 %, 95 %, and 91 %. The interobserver agreement of polyp diagnosis improved from 0.46 (95 %CI 0.30 - 0.64) before to 0.66 (95 %CI 0.48 - 0.82) after training. The trainees demonstrated that the SIMPLE classification is applicable across endoscopy platforms, with similar post-training accuracies for narrow-band imaging NBI classification (0.69; 95 %CI 0.64 - 0.73) and SIMPLE (0.71; 95 %CI 0.67 - 0.75). CONCLUSIONS: Using the I-SCAN OE system, the new SIMPLE classification demonstrated a high degree of accuracy for adenoma diagnosis, meeting the ASGE PIVI recommendations. We demonstrated that SIMPLE may be used with either I-SCAN OE or NBI.
EVALuna2:208001

Efficacy, safety, and pharmacokinetics after switching from infliximab originator to biosimilar SB2 in inflammatory bowel disease patients: A long-term observational, prospective cohort study - Fischer, Sören; Mesfin, Sarah Ellen; Klenske, E.; Schmitt, Heike; Vitali, Francesco; Hirschmann, Simon; Ramming, A.; Zundler, Sebastian; Rath, Timo; Krebs, Sabine; Dörje, Frank; Uter, Wolfgang; et al. (JOURNAL OF CROHNS & COLITIS, 2020)
CRIS-Team WoS Importer:2020-04-10

Endocytoscopy for assessing histologic inflammation in ulcerative colitis: development and prospective validation of the ELECT (ErLangen Endocytoscopy in ColiTis) score (with videos) - Vitali, Francesco; Morgenstern, Nadine; Eckstein, Markus; Atreya, Raja; Waldner, Maximilian; Hartmann, Arndt; Neurath, Markus; Rath, Timo (Gastrointestinal Endoscopy, 2022)
Background and Aims: Apart from endoscopic healing as an established treatment goal in patients with inflammatory bowel disease (IBD), histologic remission is an emerging endpoint that might even better predict disease outcome, especially in ulcerative colitis (UC). Within this study, we aimed to evaluate whether endocytoscopy (EC) as an in vivo contact microscopy technology can accurately assess histologic inflammation and predict the further course of disease in UC patients. Methods: Initially, a new and intuitive EC score reflecting the entire spectrum of microscopic disease activity in UC was consensually developed. Subsequently, this score was independently validated in 46 patients with UC who underwent close-meshed follow-up during which major adverse outcomes (MAOs; defined as disease flare, IBD-related hospitalization, IBD-related surgery, necessity for initiation or escalation therapy) were recorded. Results of EC grading of inflammatory activity were compared against 2 validated histologic scores in UC. Diagnostic performance of endoscopic remission under white-light endoscopy (Mayo Endoscopic Score and Ulcerative Colitis Endoscopic Index of Severity), EC, and histology were compared for the prediction of MAOs. Results: Endocytoscopic assessment of inflammatory activity in UC based on the newly developed ErLangen Endocytoscopy in ColiTis score showed strong correlation with histopathologic scoring (Robarts Histopathology Index, r = .70; Nancy Histologic Index, r = .73) and was superior to white-light endoscopy for grading of microscopic disease activity, with a sensitivity of 88%, specificity of 95.2%, and area under the curve of .916. Furthermore, EC exhibited a high interobserver agreement for in vivo grading of microscopic inflammation and was comparably accurate as histopathology for forecasting the occurrence of MAOs in UC. Conclusions: Endocytoscopic grading of inflammatory activity along a newly developed scoring system enabled real-time histology in UC patients and better predicted clinical outcome in UC patients than endoscopic remission.
CRIS-Team Scopus Importer:2022-12-16

Endoscopic management of buried bumper syndrome using a novel grasping-type scissor forceps - Rath, Timo; Vitali, Francesco; Naegel, Andreas; Neurath, Markus (Endoscopy, 2021)
CRIS-Team WoS Importer:2021-01-29

Endoscopic recanalization of complete esophageal obstruction - Vitali, Francesco; Naegel, Andreas; Pfeifer, Lukas; Goetz, Martin; Neurath, Markus; Rath, Timo; Siebler, Jürgen (Surgical Endoscopy, 2021)
Background and aims Complete esophageal obstruction (CEO) is a rare complication after radiochemotherapy that dramatically impairs quality of life. Within this study, we assessed the outcome of two different endoscopic techniques for lumen restoration in patients with CEO.
CRIS-Team WoS Importer:2021-02-26

Endoscopic remission assessed with PICaSSO virtual electronic chromendoscopy accurately predicts clinical outcomes in ulcerative colitis - Nardone, Olga Maria; Bazarova, Alina; Bhandari, Pradeep; Cannatelli, Rosanna; Daperno, Marco; Ferraz, Jose; Goetz, Martin; Gui, Xianyong; Hayee, Bu; De Hertogh, Gert; Lazarev, Mark; Li, Ji; et al. (United European Gastroenterology Journal, 2022)
Background and Aims: A composite endoscopic-histologic remission is increasingly explored as an important endpoint in ulcerative colitis (UC). We investigated combined endoscopic-histologic remission for predicting clinical outcomes at 12 months compared with endoscopic remission alone using the high definition virtual chromoendoscopy (VCE) Paddington International virtual ChromoendoScopy ScOre (PICaSSO) and histology scores. Methods: Ulcerative colitis patients, prospectively enrolled from 11 international centres, underwent VCE with targeted biopsies and followed up for 12 months. Endoscopic activity was assessed by Mayo Endoscopic Score (MES), Ulcerative Colitis Endoscopic Index Severity (UCEIS) followed by VCE-PICaSSO. Robarts Histopathological Index|Robarts Histological index≤3 without neutrophils in mucosa, and Nancy Histological index (NHI)≤ 1 were used to define histologic remission. Combined endoscopic-histologic remission was compared with endoscopic remission alone by Cox proportional hazards model and by two- and three-proportion analysis using pre-specified clinical outcomes. Results: 307 patients were recruited and 302 analysed. There was no difference in survival without specified clinical outcomes between PICaSSO defined endoscopic remission alone and endoscopic plus histologic remission in the rectum (HR 0.42, 95%CI 0.16-1.11 and HR 1.03, 95%CI 0.42-2.52 for Robarts Histological index and NHI respectively) at 12 months. There was however a significant survival advantage without specified clinical outcome events for UCEIS combined with histology compared with UCEIS alone (HR 0.30, 95%CI 0.12-0.75, p = 0.02) at 12 months (but not combined with NHI). For MES there was no advantage for predicting specified clinical outcomes at 12 months for endoscopy alone versus endoscopy plus histology, but there were differences in two and three proportion analysis at 6 months. Conclusion: Endoscopic remission by VCE-PICaSSO alone was similar to combined endoscopic and histologic remission for predicting specified clinical outcomes at 12 months. Larger studies with specific therapeutic interventions are required to further confirm the findings.
CRIS-Team Scopus Importer:2022-03-04
Keywords: endoscopic remission; histological remission; mucosal healing; ulcerative colitis; virtual electronic chromoendoscopy - PICaSSO – clinical outcomes – prediction

Endoscopy in Inflammatory Bowel Diseases: From Proven to New Endoskopie bei chronisch entzündlichen Darmerkrankungen: Neues und Bewährtes - Rath, Timo; Neurath, Markus (Deutsche Medizinische Wochenschrift, 2025)
Inflammatory bowel diseases with the 2 main forms - ulcerative colitis and Crohn's disease - are chronic relapsing diseases of the gastrointestinal tract in which dysregulation of the intestinal immune system against commensal components of the microbiome leads to perpetuated intestinal inflammation based on a genetic predisposition. While in the past symptom control was the focus of therapy, more recent data show that achieving endoscopic remission is superior to sole clinical symptom control for the further course and prognosis of the diseases. In this review article, we will present the significance of endoscopy for inflammatory bowel diseases, describe established scoring systems for endoscopic graduation of inflammatory activity and, last but not least, also present and review new endoscopic developments.
CRIS-Team Scopus Importer:2025-05-30
Keywords: colonoscopy; confocal laser endomicroscopy; Crohn's disease; endocytoscopy; endoscopy; inflammatory bowel diseases; ulcerative Colitis

EVALUATION OF A REAL-TIME ARTIFICIAL INTELLIGENCE SYSTEM USING A DEEP NEURAL NETWORK FOR POLYP DETECTION AND LOCALIZATION IN THE LOWER GASTROINTESTINAL TRACT - Seibt, Hannes; Beyer, Albert; Hafner, Michael; Eggert, Christian; Huber, Harald; Rath, Timo (GASTROINTESTINAL ENDOSCOPY, 2020)
CRIS-Team WoS Importer:2021-02-19

FcRn is a CD32a coreceptor that determines susceptibility to IgG immune complex-driven autoimmunity - Hubbard, Jonathan J.; Pyzik, Michal; Rath, Timo; Kozicky, Lisa K.; Sand, Kine M. K.; Gandhi, Amit K.; Grevys, Algirdas; Foss, Stian; Menzies, Susan C.; Glickman, Jonathan N.; Fiebiger, Edda; Roopenian, Derry C.; et al. (Journal of Experimental Medicine, 2020)
IgG immune complexes (ICs) promote autoimmunity through binding fragment crystallizable (Fc) gamma-receptors (FcyRs). Of these, the highly prevalent FcyRIIa (CD32a(H)) histidine (H)-131 variant (CD32(H)) is strongly linked to human autoimmune diseases through unclear mechanisms. We show that, relative to the CD32a arginine (R)-131 (CD32a(R)) variant, CD32a(H) more avidly bound human (h) IgG' IC and formed a ternary complex with the neonatal Fc receptor (FcRn) under acidic conditions. In primary human and mouse cells, both CD32a variants required FcRn to induce innate and adaptive immune responses to hIgG1 ICs, which were augmented in the setting of CD32a(H). Conversely, FcRn induced responses to IgG IC independently of classical FcyR, but optimal responses required FcRn and FcyR. Finally, FcRn blockade decreased inflammation in a rheumatoid arthritis model without reducing circulating autoantibody levels, providing support for FcRn's direct role in IgG IC-associated inflammation. Thus, CD32a and FcRn coregulate IgG IC-mediated immunity in a manner favoring the CD32a(H) variant, providing a novel mechanism for its disease association.
CRIS-Team WoS Importer:2020-11-13

FLAMINGO SET FOR THE ENDOSCOPIC TREATMENT OF BURIED BUMPER SYNDROME: MULTICENTRE, RETROSPECTIVE, COHORT STUDY - Costa, D.; Despott, E. J.; Woodward, J.; Kohout, P.; Rath, Timo; Scovell, L.; Gee, I.; Hindryckx, P.; Forrest, E.; Jordan, D.; Hollywood, C.; Hearing, S.; et al. (DIGESTIVE AND LIVER DISEASE, 2020)
CRIS-Team WoS Importer:2020-11-27

Food Intolerance of Unknown Origin: Caused by Mucosal Inflammation? A Pilot Study - Dieterich, Walburga; Tietz, Esther; Kohl, Matthias; Konturek, Peter C.; Rath, Timo; Neurath, Markus; Zopf, Yurdagül (Clinical and Translational Gastroenterology, 2021)
INTRODUCTION: The prevalence of patients with food intolerance (FI) has increased significantly. Immunoglobulin (Ig)E-mediated food allergies (FAs) are detected by determining IgE antibodies and skin prick test. Carbohydrate malabsorptions are clarified with breath tests. However, these diagnostic measures cannot capture all intolerances and have limitations in case of gut-mediated FI. The aims of this pilot study were to evaluate different methods to determine intestinal mucosal IgE in patients with FA and to characterize the intestinal mucosa in patients with FI of unknown origin (FH). METHODS: Patients with FA and FH were compared with healthy controls. To determine the IgE antibodies and the cytokines tumor necrosis factor (TNF)-α and interferon (IFN)-γ of the intestinal mucosal, a lavage was performed as part of an ileocolonoscopy and samples were taken using the cytobrush and biopsy forceps. In a subgroup, mucosal samples were also taken from the duodenum. RESULTS: Data in homogenates of intestinal mucosal samples yielded the highest sensitivity for IgE antibody titers compared with lavage and cytobrush. Patients with FA presented increased intestinal TNF-α and low IFN-γ values. This was in contrast to FH patients, who showed low intestinal IgE antibodies and TNF-α levels, but increased IFN-γ values. DISCUSSION: The determination of IgE antibodies to diagnose intestinal IgE-mediated FA is most reliable in intestinal mucosal samples. Increased TNF-α and low IFN-γ levels in patients with FA characterize an allergic reaction. Decreased TNF-α and increased IFN-γ levels in patients with FH indicate an inflammation-related intolerance reaction (see Visual Abstract, Supplementary Digital Content 1, http://links.lww.com/CTG/A520).
CRIS-Team Scopus Importer:2021-04-16

Functional molecular network analysis enables prediction of response to vedolizumab therapy in anti-TNF refractory IBD patients - Breidert, Matthias; Eftekhari, Pierre; Louis, François; Rotoiu, Claudia; Rath, Timo; Neurath, Markus; Atreya, Raja (Crohn's & Colitis 360, 2020)
Background: We applied for the first time 2 label-free technologies, physiological intermolecular modulation spectroscopy (PIMS) and nematic protein organization technic (NPOT) in anti-tumor necrosis factor (TNF) refractory inflammatory bowel disease (IBD) patients to identify clinical responders to vedolizumab therapy and elucidate their underlying functional molecular network. Methods: PIMS analysis was performed in peripheral blood taken prior to the first vedolizumab application in 20 IBD patients (Crohn disease n = 13; ulcerative colitis n = 7) refractory to at least 1 previous anti-TNF agent therapy. Peripheral blood taken from clinical responders and nonresponders at week 14 of vedolizumab therapy were additionally subjected to NPOT analysis. Response to therapy was assessed by respective clinical disease activity scores (partial Mayo Score and Harvey-Bradshaw Index). Results: Clinical response to vedolizumab treatment was observed in 7 of 13 Crohn disease and 4 of 7 ulcerative colitis patients at week 14. Response to therapy was accurately predicted by PIMS blood analysis in 100% of ulcerative colitis and 77% of Crohn disease patients. Overall prediction of clinical response with PIMS blood analysis was achieved with a 89% positive predictive value and a 82% negative predictive value. NPOT analysis revealed the heightened expression of the proteins ITGB7, ITGAV, ITG3, PF4, and ASGH in the peripheral blood of vedolizumab responders compared to nonresponders. Conclusions: PIMS analysis of the blood of anti-TNF refractory IBD patients was able to stratify responders to vedolizumab therapy with high accuracy and specificity. NPOT technology could decipher underling molecular networks in the blood of responders, enabling subsequent personalized therapeutic approaches in IBD.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Anti-TNF antibody; Inflammatory bowel disease; Nematic protein organization technic (NPOT); Physiological intermolecular modification spectroscopy (PIMS); Responder interactors; Vedolizumab

Healing of the epithelial barrier in the ileum is superior to endoscopic and histologic remission for predicting major adverse outcomes in ulcerative colitis - Rath, Timo; Atreya, Raja; Bodenschatz, Julia; Uter, Wolfgang; Geppert, Carol-Immanuel; Vitali, Francesco; Zundler, Sebastian; Waldner, Maximilian; Hartmann, Arndt; Neurath, Markus (Frontiers in Medicine, 2023)
Background: Achieving endoscopic remission is a key therapeutic goal in patients with ulcerative colitis (UC) that is associated with favorable long-term disease outcomes. Here, we prospectively compared the predictive value of endoscopic and/or histologic remission against ileal barrier healing for predicting long-term disease behavior in a large cohort of UC patients in clinical remission. Methods: At baseline, UC patients in clinical remission underwent ileocolonoscopy with assessment of ileal barrier function by confocal endomicroscopy. Endoscopic and histologic disease activity and ileal barrier healing were scored using validated scores. During subsequent follow-up (FU), patients were closely monitored for clinical disease activity and occurrence of major adverse outcomes (MAO) defined as the following: disease relapse; UC-related hospitalization; UC-related surgery; necessity for initiation or dose escalation of systemic steroids, immunosuppressants, small molecules or biological therapy. Results: Of the 73 UC patients included, 67% experienced MAO during a mean FU of 25 months. The probability of MAO-free survival was significantly higher in UC patients with endoscopic and/or histologic remission compared to patients with endoscopically and/or histologically active disease. Ileal barrier healing on endomicroscopy was highly accurate for predicting the further course of UC and outcompeted endoscopic and histologic remission for predicting MAO-free survival. Conclusion: Ileal barrier healing in clinically remittent UC patients can accurately predict future MAO development and is superior in its predictive capabilities than endoscopic and histologic remission. Ileal barrier healing therefore represents a novel and superior surrogate parameter for stratification of UC patients according to their risk for development of complicated disease behavior. Clinical trial registration: https://classic.clinicaltrials.gov/ct2/show/NCT05157750, identifier NCT05157750.
CRIS-Team Scopus Importer:2023-11-03
Keywords: endoscopy; histology; inflammatory bowel diseases; intestinal barrier; ulcerative colitis

Hobit- and Blimp-1-driven CD4(+) tissue-resident memory T cells control chronic intestinal inflammation - Zundler, Sebastian; Becker, Emily; Spocinska, Marta; Slawik, Monique; Parga-Vidal, Loreto; Stark, Regina; Wiendl, Maximilian; Atreya, Raja; Rath, Timo; Leppkes, Moritz; Hildner, Kai; Lopez Posadas, Rocío; et al. (Nature Immunology, 2019)
Although tissue-resident memory T cells (T-RM cells) have been shown to regulate host protection in infectious disorders, their function in inflammatory bowel disease (IBD) remains to be investigated. Here we characterized T-RM cells in human IBD and in experimental models of intestinal inflammation. Pro-inflammatory T-RM cells accumulated in the mucosa of patients with IBD, and the presence of CD4(+)CD69(+)CD103(+) T-RM cells was predictive of the development of flares. In vivo, functional impairment of T-RM cells in mice with double knockout of the T-RM-cell-associated transcription factors Hobit and Blimp-1 attenuated disease in several models of colitis, due to impaired cross-talk between the adaptive and innate immune system. Finally, depletion of T-RM cells led to a suppression of colitis activity. Together, our data demonstrate a central role for T-RM cells in the pathogenesis of chronic intestinal inflammation and suggest that these cells could be targets for future therapeutic approaches in IBD.
CRIS-Team WoS Importer:2019-03-06

IFN-γ drives inflammatory bowel disease pathogenesis through VE-cadherin-directed vascular barrier disruption - Langer, Victoria; Vivi, Eugenia; Regensburger, Daniela; Winkler, Thomas; Waldner, Maximilian; Rath, Timo; Schmid, Benjamin; Skottke, Lisa; Lee, Somin; Jeon, Noo Li; Wohlfahrt, Thomas; Kramer, Viktoria; et al. (Journal of Clinical Investigation, 2019)
Inflammatory bowel disease (IBD) is a chronic inflammatory disorder with rising incidence. Diseased tissues are heavily vascularized. Surprisingly, the pathogenic impact of the vasculature in IBD and the underlying regulatory mechanisms remain largely unknown. IFN-γ is a major cytokine in IBD pathogenesis, but in the context of the disease, it is almost exclusively its immune-modulatory and epithelial cell-directed functions that have been considered. Recent studies by our group demonstrated that IFN-γ also exerts potent effects on blood vessels. Based on these considerations, we analyzed the vessel-directed pathogenic functions of IFN-γ and found that it drives IBD pathogenesis through vascular barrier disruption. Specifically, we show that inhibition of the IFN-γ response in vessels by endothelial-specific knockout of IFN-γ receptor 2 ameliorates experimentally induced colitis in mice. IFN-γ acts pathogenic by causing a breakdown of the vascular barrier through disruption of the adherens junction protein VE-cadherin. Notably, intestinal vascular barrier dysfunction was also confirmed in human IBD patients, supporting the clinical relevance of our findings. Treatment with imatinib restored VE-cadherin/adherens junctions, inhibited vascular permeability, and significantly reduced colonic inflammation in experimental colitis. Our findings inaugurate the pathogenic impact of IFN-γ-mediated intestinal vessel activation in IBD and open new avenues for vascular-directed treatment of this disease.

IL-13 as Target to Reduce Cholestasis and Dysbiosis in Abcb4 Knockout Mice - Hahn, Luisa; Helmrich, Nora; Herebian, Diran; Mayatepek, Ertan; Drebber, Uta; Domann, Eugen; Olejniczak, Stefan; Weigel, Markus; Hain, Torsten; Rath, Timo; Wirtz, Stefan; Mollenkopf, Hans Joachim; et al. (Cells, 2020)
The Th2 cytokine IL-13 is involved in biliary epithelial injury and liver fibrosis in patients as well as in animal models. The aim of this study was to investigate IL-13 as a therapeutic target during short term and chronic intrahepatic cholestasis in an Abcb4-knockout mouse model (Abcb4-/-). Lack of IL-13 protected Abcb4-/- mice transiently from cholestasis. This decrease in serum bile acids was accompanied by an enhanced excretion of bile acids and a normalization of fecal bile acid composition. In Abcb4-/-/IL-13-/- double knockout mice, bacterial translocation to the liver was significantly reduced and the intestinal microbiome resembled the commensal composition in wild type animals. In addition, 52-week-old Abcb4-/-IL-13-/- mice showed significantly reduced hepatic fibrosis. Abcb4-/- mice devoid of IL-13 transiently improved cholestasis and converted the composition of the gut microbiota towards healthy conditions. This highlights IL-13 as a potential therapeutic target in biliary diseases.
CRIS-Team Scopus Importer:2020-09-25
Keywords: bacterial translocation; bile acid; intestinal microbiome; liver fibrosis; Th2; tight junction

IL-20 controls resolution of experimental colitis by regulating epithelial IFN/STAT2 signalling - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Günther, Claudia; Gonzalez Acera, Miguel; Atreya, Raja; Stolzer, Iris; Wittner, Leonie; Dressel, Anja; Schickedanz, Laura; Gámez Belmonte, Maria de los Reyes; Erkert, Lena; Hundorfean, Gheorghe; et al. (Gut, 2023)
Objective: We sought to investigate the role of interleukin (IL)-20 in IBD and experimental colitis. Design: Experimental colitis was induced in mice deficient in components of the IL-20 and signal transducer and activator of transcription (STAT)2 signalling pathways. In vivo imaging, high-resolution mini-endoscopy and histology were used to assess intestinal inflammation. We further used RNA-sequencing (RNA-Seq), RNAScope and Gene Ontology analysis, western blot analysis and co-immunoprecipitation, confocal microscopy and intestinal epithelial cell (IEC)-derived three-dimensional organoids to investigate the underlying molecular mechanisms. Results were validated using samples from patients with IBD and non-IBD control subjects by a combination of RNA-Seq, organoids and immunostainings. Results: In IBD, IL20 levels were induced during remission and were significantly higher in antitumour necrosis factor responders versus non-responders. IL-20RA and IL-20RB were present on IECs from patients with IBD and IL-20-induced STAT3 and suppressed interferon (IFN)-STAT2 signalling in these cells. In IBD, experimental dextran sulfate sodium (DSS)-induced colitis and mucosal healing, IECs were the main producers of IL-20. Compared with wildtype controls, Il20-/-, Il20ra-/- and Il20rb-/- mice were more susceptible to experimental DSS-induced colitis. IL-20 deficiency was associated with increased IFN/STAT2 activity in mice and IFN/STAT2-induced necroptotic cell death in IEC-derived organoids could be markedly blocked by IL-20. Moreover, newly generated Stat2ΔIEC mice, lacking STAT2 in IECs, were less susceptible to experimental colitis compared with wildtype controls and the administration of IL-20 suppressed colitis activity in wildtype animals. Conclusion: IL-20 controls colitis and mucosal healing by interfering with the IFN/STAT2 death signalling pathway in IECs. These results indicate new directions for suppressing gut inflammation by modulating IL-20-controlled STAT2 signals.
CRIS-Team Scopus Importer:2023-11-17
Keywords: experimental colitis; inflammatory bowel disease; interferon; interleukins; signal transduction

Inhibiting Interleukin 36 Receptor Signaling Reduces Fibrosis in Mice with Chronic Intestinal Inflammation - Scheibe, Kristina; Kersten, Christina; Schmied, Anabel; Vieth, Michael; Primbs, Tatjana; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Claussen, Jing; Klimowicz, Alexander C.; Zheng, Jie; Baum, Patrick; Meyer, Sebastian; et al. (Gastroenterology, 2018)
BACKGROUND & AIMS: Intestinal fibrosis is a long-term complication in inflammatory bowel diseases (IBD) frequently resulting in functional damage, bowel obstruction, and surgery. Interleukin 36 (IL36) is a group of cytokines in the IL1 family with inflammatory effects. We studied expression of IL36 and its receptor, interleukin 1 receptor like 2 (IL1RL2 or IL36R) in development of intestinal fibrosis in human tissues and mice. METHODS: We obtained intestinal tissues from 92 patients with Crohn´s disease (CD), 48 patients with ulcerative colitis (UC), and 26 patients without inflammatory bowel diseases (controls). Tissues were analyzed by histology to detect fibrosis and immunohistochemistry to determine the distribution of fibroblasts and levels of IL36R ligands. Human and mouse fibroblasts were incubated with IL36 or control medium, and transcriptome-wide RNA sequences were analyzed. Mice were given neutralizing antibodies against IL36R and we studied intestinal tissues from Il1rl2-/- mice; colitis and fibrosis was induced in mice by repetitive administration of DSS or TNBS. Bone marrow cells were transplanted from Il1rl2-/- to irradiated wild-type mice and intestinal tissues were analyzed. Antibodies against IL36R were applied to mice with established chronic colitis and fibrosis and intestinal tissues were studied. RESULTS: Mucosal and submucosal tissues from patients with CD or UC had higher levels of collagens including type VI collagen compared to tissues from controls. In tissues from patients with fibrostenotic CD, significantly higher levels of IL36A were noted, which correlated with high numbers of activated fibroblasts that expressed alpha smooth muscle actin. IL36R activation of mouse and human fibroblasts resulted in expression of genes that regulate fibrosis and tissue remodeling, as well as expression of collagen type VI. Il1rl2-/- mice and mice given injections of an antibody against IL36R developed less severe colitis and fibrosis following administration of DSS or TNBS, but bone marrow cells from Il1rl2-/- mice did not prevent induction of colitis and fibrosis. Injection of antibodies against IL36R significantly reduced established fibrosis in mice with chronic intestinal inflammation. CONCLUSION: We found higher levels of IL36A in fibrotic intestinal tissues from patients with IBD, compared with controls. IL36 induced expression of genes that regulate fibrogenesis in fibroblasts. Inhibition or knockout of the IL36R in mice reduces chronic colitis and intestinal fibrosis. Agents designed to block IL36R signaling could be developed for prevention and treatment of intestinal fibrosis in patients with IBD.
EVALuna2:35123

Intestinal Barrier Healing Is Superior to Endoscopic and Histologic Remission for Predicting Major Adverse Outcomes in Inflammatory Bowel Disease: The Prospective ERIca Trial - Rath, Timo; Atreya, Raja; Bodenschatz, Julia; Uter, Wolfgang; Geppert, Carol-Immanuel; Vitali, Francesco; Fischer, Sarah; Waldner, Maximilian; Colombel, Jean Frédéric; Hartmann, Arndt; Neurath, Markus (Gastroenterology, 2023)
Background & Aims: Endoscopic and histologic remission have emerged as key therapeutic goals in the management of inflammatory bowel diseases (IBD) that are associated with favorable long-term disease outcomes. Here, we prospectively compared the predictive value of barrier healing with endoscopic and histologic remission for predicting long-term disease behavior in a large cohort of patients with IBD in clinical remission. Methods: At baseline, patients with IBD in clinical remission underwent ileocolonoscopy with assessment of intestinal barrier function by confocal endomicroscopy. Endoscopic and histologic disease activity, as well as barrier healing, was prospectively assessed along established scores. During subsequent follow-up, patients were closely monitored for clinical disease activity and the occurrence of major adverse outcomes (MAOs): disease flares, IBD-related hospitalization or surgery, and initiation or dose escalation of systemic steroids, immunosuppressants, small molecules, or biological therapy. Results: The final analysis included 181 patients, 100 with Crohn's disease [CD] and 81 with ulcerative colitis (UC). During a mean follow-up of 35 (CD) and 25 (UC) months, 73% of patients with CD and 69% of patients with UC experienced at least 1 MAO. The probability of MAO-free survival was significantly higher in patients with IBD with endoscopic remission compared with endoscopically active disease. In addition, histologic remission predicted MAO-free survival in patients with UC but not CD. Barrier healing on endomicroscopy was superior to endoscopic and histologic remission for predicting MAO-free survival in both UC and CD. Conclusions: Barrier healing is associated with decreased risk of disease progression in patients with clinically remittent IBD, with superior predictive performance compared with endoscopic and histologic remission. Analysis of barrier function might be considered as a future treatment target in clinical trials. ClinicalTrials.gov number, NCT05157750.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Confocal Laser Endomicroscopy; Endoscopy; Histology; Inflammatory Bowel Diseases; Intestinal Barrier

Is histological healing a feasible endpoint in ulcerative colitis? - Rath, Timo; Atreya, Raja; Neurath, Markus (Expert Review of Gastroenterology and Hepatology, 2021)
Introduction: Currently, treatment goals in ulcerative colitis aim to achieve clinical remission and endoscopic mucosal healing. Emerging evidence suggests that histologic assessment of inflammation is a sensitive marker that can outcompete mucosal healing in predicting the clinical course of disease in patients with ulcerative colitis. Based on this, histologic healing is frequently included as a secondary endpoint in pharmacological trials. Areas covered: We introduce currently used clinical and endoscopic treatment goals, summarize commonly used histologic scoring systems and then provide an overview on the relevance of histologic healing on the outcome in patients with ulcerative colitis. Finally, we review the efficacy of existing UC therapies for inducing histologic remission. Expert opinion: Histologic healing is achievable in a substantial portion of UC patients. Further, histologic healing is, as consolidated by several meta-analyses, associated with better disease outcome compared to clinical remission and/or endoscopic healing. However, before becoming a widely acceptable treatment endpoint, consensus definitions for histologic healing and the technical aspects as well as for the timing for obtaining biopsies are needed. And finally, we need more evidence to show that resolution of microscopic inflammation as a means of therapy change or dose escalation is indeed a superior endpoint.
CRIS-Team Scopus Importer:2021-02-12
Keywords: endoscopic healing; histologic healing; histologic remission; Inflammatory bowel diseases; mucosal healing; ulcerative colitis

Label-Free In Vivo Histopathology of Experimental Colitis via 3-Channel Multiphoton Endomicroscopy - Kreiß, Lucas; Thoma, Oana Maria; Dilipkumar, Ashwathama; Carlé, Birgitta-Elisabeth; Longequeue, Pascal; Kunert, Timo; Rath, Timo; Hildner, Kai; Neufert, Clemens; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; et al. (Gastroenterology, 2020)
CRIS-Team Scopus Importer:2020-08-28

Long-term effectiveness, safety and immunogenicity of the biosimilar SB2 in inflammatory bowel disease patients after switching from originator infliximab - Fischer, Sören; Cohnen, Sarah; Klenske, Entcho; Schmitt, Heike; Vitali, Francesco; Hirschmann, Simon; Ramming, Andreas; Zundler, Sebastian; Rath, Timo; Krebs, Sabine; Dörje, Frank; Uter, Wolfgang; et al. (Therapeutic Advances in Gastroenterology, 2021)
Background: Long-term data on inflammatory bowel disease (IBD) patients switched from originator to biosimilar infliximab SB2 are lacking. The aim of the conducted study was to investigate the effectiveness, immunogenicity and safety of a large prospectively followed-up IBD patient cohort that was entirely switched from originator infliximab to biosimilar SB2 treatment. Methods: This was a prospective, single-center, longitudinal, observational study describing clinical outcomes in IBD patients, over an 80-week period following switch from originator infliximab to SB2. Primary outcome measures were change of disease activity [Harvey-Bradshaw Index for Crohn’s disease (CD), partial Mayo Score for ulcerative colitis (UC)], C-reactive protein (CRP), infliximab trough levels (TLs), anti-drug antibodies (ADAs) and adverse events. Results: One hundred and forty-four IBD patients (94 CD, 50 UC), with median duration of 30.5 months’ (range 2–110) treatment with originator infliximab were evaluated. Mean change of disease activity compared with baseline was −0.9 (SD 2.6), –0.4 (2.2) and –0.4 (2.0) in CD; 0.1 (1.1), 0.1 (1.1) and 0.1 (1.3) in UC patients at weeks 24, 48 and 72. Median infliximab TLs were 6.2 µg/ml (interquartile range 2.3–12.2), 5.0 µg/ml (2.7–10.0), 6.6 µg/ml (3.5–12.4) and 5.1 µg/ml (2.7–10.9) at baseline and weeks 24, 48 and 72. Median CRP levels were within normal ranges throughout the study. After the switch, 9.8% of the patients developed new ADAs. Persistence on SB2 was 90% (95% confidence interval 0.85–0.95), 79% (0.72–0.86), 72% (0.64–0.80) at weeks 26, 52 and 78. Serious adverse events occurred in 11 patients. Conclusion: Over the individual patient follow-up of 80 weeks, switch to biosimilar SB2 from originator infliximab does not result in increased disease activity or changed immunogenicity patterns. The switch to SB2 was well tolerated.
CRIS-Team Scopus Importer:2021-02-05
Keywords: biosimilar; inflammatory bowel diseases; infliximab; SB2; switch

Long-term outcomes of cyclosporin induction and ustekinumab maintenance combination therapy in patients with steroid-refractory acute severe ulcerative colitis - Vitali, Francesco; Rath, Timo; Klenske, Entcho; Vögele, Anna-Lena; Ganzleben, Ingo; Zundler, Sebastian; Strobel, Deike; Geppert, Carol-Immanuel; Hartmann, Arndt; Neurath, Markus; Atreya, Raja (Therapeutic Advances in Gastroenterology, 2024)
Background: Effective management of patients with acute severe ulcerative colitis (ASUC) is a major challenge and there remains a paucity of available maintenance treatment options after efficacious cyclosporin induction therapy. Objectives: We investigated the long-term effectiveness and safety of cyclosporin and ustekinumab combination therapy in patients with steroid refractory ASUC. Design: Monocentric, prospective study. Methods: We included patients with steroid refractory ASUC with multiple failed prior advanced therapies, who were treated with cyclosporin and ustekinumab combination therapy. Results: Among the 11 included patients, 10 had prior failure to infliximab and 8 failed at least three previous biological therapies. The mean baseline Mayo and Lichtiger scores were 10.9 (9–12) and 13.3 (11–14), respectively. Ustekinumab was initiated 3.2 weeks (1–8) after initiation of cyclosporin treatment and combination therapy was continued for a mean of 11.5 (4–20) weeks. Clinical response was achieved in six patients at week 16 and clinical steroid-free clinical remission in five patients at week 48. Endoscopic remission was achieved in five patients at week 16 and together with histological remission in five patients at week 52. Intestinal ultrasound demonstrated mean bowel wall thickening in the sigmoid colon of 5.5 mm at baseline and 3.5 mm at week 52, respectively. Two patients had to undergo colectomy (mean 4.5 months, range 3–6) and three stopped ustekinumab therapy due to ineffectiveness. Overall, combination therapy was well tolerated. Conclusion: Combination of cyclosporin and ustekinumab therapy allowed nearly half of ASUC patients to reach clinical and endoscopic remission after 52 weeks, warranting further studies. Trial registration: Not applicable.
CRIS-Team Scopus Importer:2024-01-19
Keywords: cyclosporin; proctocolectomy; severe ulcerative colitis; sonography; ustekinumab

Magnification endoscopy with optical chromoendoscopy for in vivo assessment of histological inflammation in patients with inflammatory bowel disease - Klenske, E.; Atreya, Raja; Hartmann, Arndt; Fischer, Sören; Hirschmann, Simon; Zundler, Sebastian; Iacucci, M.; Neurath, Markus; Rath, Timo (JOURNAL OF CROHNS & COLITIS, 2019)
CRIS-Team WoS Importer:2019-03-20

Magnification endoscopy with optical chromoendoscopy shows strong correlation with histologic inflammation in patients with inflammatory bowel disease - Klenske, Entcho; Atreya, Raja; Hartmann, Arndt; Fischer, Sören; Hirschmann, Simon; Zundler, Sebastian; Iaccuci, Marietta; Neurath, Markus; Rath, Timo (Endoscopy International Open, 2019)
Background and study aims Apart from mucosal healing as an established treatment goal in inflammatory bowel diseases (IBD), recent evidence suggests that histologic healing may become another key prognostic parameter in IBD patients. We aimed to evaluate whether magnification endoscopy with optical chromoendoscopy can accurately assess histologic inflammation in IBD patients.
CRIS-Team WoS Importer:2019-09-13

Maximizing the diagnostic information from biopsies in chronic inflammatory bowel diseases: recommendations from the Erlangen International Consensus Conference on Inflammatory Bowel Diseases and presentation of the IBD-DCA score as a proposal for a new index for histologic activity assessment in ulcerative colitis and Crohn's disease - Lang-Schwarz, Corinna; Agaimy, Abbas; Atreya, Raja; Becker, Christoph; Danese, Silvio; Flejou, Jean-Francois; Gassler, Nikolaus; Grabsch, Heike I.; Hartmann, Arndt; Kamaradova, Katerina; Kuehl, Anja A.; Lauwers, Gregory Y.; et al. (Virchows Archiv, 2020)
CRIS-Team WoS Importer:2021-01-22

Missed lesions and artificial intelligence during colonoscopy: the tireless working expert in the room - Rath, Timo (Endoscopy, 2021)
CRIS-Team WoS Importer:2021-12-24

Molecular Endoscopic Imaging in Cancer - Rath, Timo; Neurath, Markus; Atreya, Raja (Elsevier, 2021)
Through the combination of administration of fluorescently labeled molecular dyes that specifically bind to defined molecular targets and their subsequent visualization with endoscopic devices, molecular endoscopic imaging enables in vivo real-time imaging of single molecules or receptors.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Barrett’s esophagus; Cancer; Colorectal cancer; Endoscopy; Gastric cancer; Molecular imaging

Molecular Imaging and its Applications in Selected GI Diseases - Rath, Timo; Neurath, Markus; Atreya, Raja (Techniques and Innovations in Gastrointestinal Endoscopy, 2021)
During the past decade, molecular imaging has emerged as a new and innovative field combining clinical endoscopy with methods prior used in basic science. Through the labeling of cellular targets with certain molecular probes and their subsequent detection with dedicated endoscopic devices, molecular imaging enables the visualization of single molecules or receptors during ongoing endoscopy. Early studies in the field have provided proof-of-principle that molecular imaging can improve visualization, or even unmask, previously unrecognized early dysplasia or cancer. Building on this, further studies then used molecular imaging for grading and detecting inflammation and inflammation associated cancer. Most recently, molecular imaging has been used to phenotype the expression of single receptors and targets of biological therapy and thereby enables molecular tissue profile in vivo. With this live molecular fingerprinting, molecular imaging can be used to guide expression-tailored individualized therapy, and due to the diversification of biological therapy in both cancer and intestinal inflammation, it can be expected that molecular imaging will gain further traction in the foreseeable future. Within this review, we first summarize the technical components commonly used for molecular imaging and then review preclinical and clinical studies and possible and evolving clinical applications on molecular imaging within the entire the GI tract.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Barretts esophagus; Colorectal cancer; Endoscopy; Inflammatory bowel disease; Molecular imaging

Molecular imaging in inflammatory bowel disease - Rath, Timo; Neurath, Markus; Atreya, Raja (Elsevier, 2020)
Recent advances in biological therapy in inflammatory bowel diseases (IBDs) and early detection of colitis-associated neoplasia have increased the popularity of molecular endoscopy with visualization of single receptor or molecular target expression and the subsequent initiation of expression tailored therapy. Molecular imaging is an emerging field in the receptor expression within the mucosa on a cellular level rather than on macroscopic changes. Various new technological and molecular probes have been utilized for molecular imaging. These new technologies have found their applications in diagnosis, disease monitoring, and assessment of treatment response in IBD. They may also play a role in the detection of colitis-associated neoplasia.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Biological therapy; Crohn’s disease; endomicroscopy; inflammation; therapeutic response; ulcerative colitis

Molecular Imaging: The New Frontier for Endoscopic Diagnosis and Personalization in Inflammatory Bowel Disease - Atreya, Raja; Rath, Timo; Neurath, Markus (Gastrointestinal Endoscopy Clinics of North America, 2024)
CRIS-Team Scopus Importer:2024-10-18
Keywords: Fluorescence; Fluorescent antibody; IBD; Molecular endoscopy; Molecular imaging; Mucosa; Prediction of response; Target cell

Motorized spiral enteroscopy: Results of an international multicenter prospective observational clinical study in patients with normal and altered gastrointestinal anatomy - Beyna, Torsten; Moreels, Tom; Arvanitakis, Marianna; Pioche, Mathieu; Saurin, Jean-Christophe; May, Andrea; Knabe, Mate; Agnholt, Jorgen Steen; Bjerregaard, Niels Christian; Puustinen, Lauri; Schlag, Christoph; Aabakken, Lars; et al. (Endoscopy, 2022)
Background Motorized spiral enteroscopy (MSE) has been shown to be safe and effective for deep enteroscopy in studies performed at expert centers with limited numbers of patients without previous abdominal surgery. This study aimed to investigate the safety, efficacy, and learning curve associated with MSE in a real-life scenario, with the inclusion of patients after abdominal surgery and with altered anatomy. Methods Patients with indications for deep enteroscopy were enrolled in a prospective observational multicenter study. The primary objective was the serious adverse event (SAE) rate; secondary objectives were the diagnostic and therapeutic yield, procedural success, time, and insertion depth. Data analysis was subdivided into training and core (post-training) study phases at centers with different levels of MSE experience. Results 298 patients (120 women; median age 68, range 19-92) were enrolled. In the post-training phase, 21.5 % (n = 54) had previous abdominal surgery, 10.0 % (n = 25) had surgically altered anatomy. Overall, SAEs occurred in 2.3 % (7/298; 95 %CI 0.9 %-4.8 %). The SAE rate was 2.0 % (5/251) in the core group and 4.3 % (2/47) in the training group, and was not increased after abdominal surgery (1.9 %). Total enteroscopy was achieved in half of the patients (n = 42) undergoing planned total enteroscopy. In 295/337 procedures (87.5 %), the anatomical region of interest could be reached. Conclusions This prospective multicenter study showed that MSE was feasible and safe in a large cohort of patients in a real-life setting, after a short learning curve. MSE was shown to be feasible in postsurgical patients, including those with altered anatomy, without an increase in the SAE rate.
CRIS-Team Scopus Importer:2022-07-22

Mucosal Biofilms Are an Endoscopic Feature of Irritable Bowel Syndrome and Ulcerative Colitis - Baumgartner, Maximilian; Lang, Michaela; Holley, Hunter; Crepaz, Daniel; Hausmann, Bela; Pjevac, Petra; Moser, Doris; Haller, Felix; Hof, Fabian; Beer, Andrea; Orgler, Elisabeth; Frick, Adrian; et al. (Gastroenterology, 2021)
Background & Aims: Irritable bowel syndrome (IBS) and inflammatory bowel diseases result in a substantial reduction in quality of life and a considerable socioeconomic impact. In IBS, diagnosis and treatment options are limited, but evidence for involvement of the gut microbiome in disease pathophysiology is emerging. Here we analyzed the prevalence of endoscopically visible mucosal biofilms in gastrointestinal disease and associated changes in microbiome composition and metabolism. Methods: The presence of mucosal biofilms was assessed in 1426 patients at 2 European university-based endoscopy centers. One-hundred and seventeen patients were selected for in-depth molecular and microscopic analysis using 16S ribosomal RNA gene amplicon-sequencing of colonic biopsies and fecal samples, confocal microscopy with deep learning–based image analysis, scanning electron microscopy, metabolomics, and in vitro biofilm formation assays. Results: Biofilms were present in 57% of patients with IBS and 34% of patients with ulcerative colitis compared with 6% of controls (P < .001). These yellow-green adherent layers of the ileum and right-sided colon were microscopically confirmed to be dense bacterial biofilms. 16S-sequencing links the presence of biofilms to a dysbiotic gut microbiome, including overgrowth of Escherichia coli and Ruminococcus gnavus. R. gnavus isolates cultivated from patient biofilms also formed biofilms in vitro. Metabolomic analysis found an accumulation of bile acids within biofilms that correlated with fecal bile acid excretion, linking this phenotype with a mechanism of diarrhea. Conclusions: The presence of mucosal biofilms is an endoscopic feature in a subgroup of IBS and ulcerative colitis with disrupted bile acid metabolism and bacterial dysbiosis. They provide novel insight into the pathophysiology of IBS and ulcerative colitis, illustrating that biofilm can be seen as a tipping point in the development of dysbiosis and disease.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Bacterial–Epithelial Interaction; Endoscopy; Functional Gastrointestinal Disorders; Microbiota

Multicenter cohort study of patients with buried bumper syndrome treated endoscopically with a novel, dedicated device - Costa, Deborah; Despott, Edward J.; Lazaridis, Nikolaos; Woodward, Jeremy; Kohout, Pavel; Rath, Timo; Scovell, Louise; Gee, Ian; Hindryckx, Pieter; Forrest, Ewan; Hollywood, Coral; Hearing, Stephen; et al. (Gastrointestinal Endoscopy, 2021)
Background and Aims: Buried bumper syndrome (BBS) is a rare adverse event of percutaneous endoscopic gastrostomy (PEG) placement in which the internal bumper migrates through the stomal tract to become embedded within the gastric wall. Excessive tension between the internal and external bumpers, causing ischemic necrosis of the gastric wall, is believed to be the main etiologic factor. Several techniques for endoscopic management of BBS have been described using off-label devices. The Flamingo set is a novel, sphincterotome-like device specifically designed for BBS management. We aimed to evaluate the effectiveness of the Flamingo device in a large, homogeneous cohort of patients with BBS. Methods: A guidewire was inserted through the external access of the PEG tube into the gastric lumen. The Flamingo device was then introduced into the stomach over the guidewire. This dedicated tool can be flexed by 180 degrees, exposing a sphincterotome-like cutting wire, which is used to incise the overgrown tissue until the PEG bumper is exposed. A retrospective, international, multicenter cohort study was conducted on 54 patients between December 2016 and February 2019. Results: The buried bumper was successfully removed in 53 of 55 procedures (96.4%). The median time for the endoscopic removal of the buried bumper was 22 minutes (range, 5-60). Periprocedural endoscopic adverse events occurred in 7 procedures (12.7%) and were successfully managed endoscopically. A median follow-up of 150 days (range, 33-593) was performed in 29 patients (52.7%), during which no significant adverse events occurred. Conclusions: Through our experience, we found this dedicated novel device to be safe, quick, and effective for minimally invasive, endoscopic management of BBS.
CRIS-Team Scopus Importer:2021-02-12

NLRP3 Inhibition Leads to Impaired Mucosal Fibroblast Function in Patients with Inflammatory Bowel Diseases - Weber, Simone; Sitte, Selina; Vögele, Anna-Lena; Sologub, Ludmilla; Wilfer, Angelika; Rath, Timo; Nägel, Andreas; Zundler, Sebastian; Franchi, Luigi; Opipari, Anthony W.; Sonnewald, Sophia; Reid, Stephen; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: Inflammatory bowel diseases (IBD) are characterized by mucosal inflammation and sequential fibrosis formation, but the exact role of the hyperactive NLRP3 inflammasome in these processes is unclear. Thus, we studied the expression and function of the NLRP3 inflammasome in the context of inflammation and fibrosis in IBD. Methods: We analysed intestinal NLRP3 expression in mucosal immune cells and fibroblasts from IBD patients and NLRP3-associated gene expression via single-cell RNA sequencing and microarray analyses. Furthermore, cytokine secretion of NLRP3 inhibitor treated blood and mucosal cells, as well as proliferation, collagen production, and cell death of NLRP3 inhibitor treated intestinal fibroblasts from IBD patients were studied. Results: We found increased NLRP3 expression in the inflamed mucosa of IBD patients and NLRP3 inhibition led to reduced IL-1β and IL-18 production in blood cells and diminished the bioactive form of mucosal IL-1β. Single cell analysis identified overlapping expression patterns of NLRP3 and IL-1β in classically activated intestinal macrophages and we also detected NLRP3 expression in CD163+ macrophages. In addition, NLRP3 expression was also found in intestinal fibroblasts from IBD patients. Inhibition of NLRP3 led to reduced proliferation of intestinal fibroblasts, which was associated with a marked decrease in production of collagen type I and type VI in IBD patients. Moreover, NLRP3 inhibition in intestinal fibroblasts induced autophagy, a cellular process involved in collagen degradation. Conclusions: In the presented study, we demonstrate that inhibiting NLRP3 might pave the way for novel therapeutic approaches in IBD, especially to prevent the severe complication of intestinal fibrosis formation.
CRIS-Team Scopus Importer:2023-11-17
Keywords: fibroblasts; fibrosis; IL-18; IL-1β; Inflammatory bowel diseases; mucosal immune system; NLRP3 inflammasome; small molecule inhibitor

Non-classical monocyte homing to the gut via α4β7 integrin mediates macrophage-dependent intestinal wound healing - Schleier, Lena; Wiendl, Maximilian; Heidbreder, Karin; Binder, Marie Theres; Atreya, Raja; Rath, Timo; Becker, Elisabeth; Schulz-Kuhnt, Anja; Stahl, Annette; Schulze, Lisa; Ullrich, Karen; Merz, Simon F.; et al. (Gut, 2019)
Objective: To study the role of α4β7 integrin for gut homing of monocytes and to explore the biological consequences of therapeutic α4β7 inhibition with regard to intestinal wound healing. Design: We studied the expression of homing markers on monocyte subsets in the peripheral blood and on macrophage subsets in the gut of patients with IBD and controls with flow cytometry and immunohistochemistry. Integrin function was addressed with dynamic adhesion assays and in vivo gut homing assays. In vivo wound healing was studied in mice deficient for or depleted of α4β7 integrin. Results: Classical and non-classical monocytes were clearly dichotomous regarding homing marker expression including relevant expression of α4β7 integrin on human and mouse non-classical monocytes but not on classical monocytes. Monocyte-expressed α4β7 integrin was functionally important for dynamic adhesion to mucosal vascular addressin cell adhesion molecule 1 and in vivo gut homing. Impaired α4β7-dependent gut homing was associated with reduced (effect size about 20%) and delayed wound healing and suppressed perilesional presence of wound healing macrophages. Non-classical monocytes in the peripheral blood were increased in patients with IBD under clinical treatment with vedolizumab. Conclusion: In addition to reported effects on lymphocytes, anti-α4β7 therapy in IBD also targets non-classical monocytes. Impaired gut homing of such monocytes might lead to a reduction of wound healing macrophages and could potentially explain increased rates of postoperative complications in vedolizumab-treated patients, which have been observed in some studies.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Crohn's disease; gut immunology; inflammatory bowel disease; surgery for IBD; ulcerative colitis

Non-invasive assessment of intestinal inflammatory activity in Ulcerative Colitis by Multispectral Optoacoustic Tomography (MSOT) - Klett, Daniel; Jesper, D.; Vitali, Francesco; Federle, Anna; Atreya, Raja; Strobel, Deike; Leppkes, Moritz; Neufert, Clemens; Rath, Timo; Neurath, Markus; Waldner, Maximilian (JOURNAL OF CROHNS & COLITIS, 2022)
CRIS-Team WoS Importer:2022-05-13

Perforations after routine biopsy in IBD patients, their management and potential risk reductions by microscopic imaging with endocytoscopy - Klenske, Entcho; Hartmann, Arndt; Atreya, Raja; Neurath, Markus; Rath, Timo (Journal of Gastrointestinal and Liver Diseases, 2020)
CRIS-Team Scopus Importer:2020-09-25

PICaSSO Histologic Remission Index (PHRI) in ulcerative colitis: development of a novel simplified histological score for monitoring mucosal healing and predicting clinical outcomes and its applicability in an artificial intelligence system - Gui, Xianyong; Bazarova, Alina; Del Amor, Rocio; De Hertogh, Gert; Villanacci, Vincenzo; Zardo, Davide; Parigi, Tommaso Lorenzo; Royset, Elin Synnove; Shivaji, Uday N.; Monica, Melissa Anna Teresa; Mandelli, Giulio; Bhandari, Pradeep; et al. (Gut, 2022)
Histological remission is evolving as an important treatment target in UC. We aimed to develop a simple histological index, aligned to endoscopy, correlated with clinical outcomes, and suited to apply to an artificial intelligence (AI) system to evaluate inflammatory activity. Methods Using a set of 614 biopsies from 307 patients with UC enrolled into a prospective multicentre study, we developed the Paddington International virtual ChromoendoScopy ScOre (PICaSSO) Histologic Remission Index (PHRI). Agreement with multiple other histological indices and validation for inter-reader reproducibility were assessed. Finally, to implement PHRI into a computer-aided diagnosis system, we trained and tested a novel deep learning strategy based on a CNN architecture to detect neutrophils, calculate PHRI and identify active from quiescent UC using a subset of 138 biopsies. Results PHRI is strongly correlated with endoscopic scores (Mayo Endoscopic Score and UC Endoscopic Index of Severity and PICaSSO) and with clinical outcomes (hospitalisation, colectomy and initiation or changes in medical therapy due to UC flare-up). A PHRI score of 1 could accurately stratify patients' risk of adverse outcomes (hospitalisation, colectomy and treatment optimisation due to flare-up) within 12 months. Our inter-reader agreement was high (intraclass correlation 0.84). Our preliminary AI algorithm differentiated active from quiescent UC with 78% sensitivity, 91.7% specificity and 86% accuracy. Conclusions PHRI is a simple histological index in UC, and it exhibits the highest correlation with endoscopic activity and clinical outcomes. A PHRI-based AI system was accurate in predicting histological remission.
CRIS-Team WoS Importer:2022-03-04

Real-time colorectal polyp detection using a novel computer-aided detection system (CADe): a feasibility study - Soons, E.; Rath, Timo; Hazewinkel, Y.; Van Dop, W. A.; Esposito, D.; Testoni, P. A.; Siersema, P. D. (International Journal of Colorectal Disease, 2022)
Background and aims Colonoscopy aims to early detect and remove precancerous colorectal polyps, thereby preventing development of colorectal cancer (CRC). Recently, computer-aided detection (CADe) systems have been developed to assist endoscopists in polyp detection during colonoscopy. The aim of this study was to investigate feasibility and safety of a novel CADe system during real-time colonoscopy in three European tertiary referral centers. Methods Ninety patients undergoing colonoscopy assisted by a real-time CADe system (DISCOVERY; Pentax Medical, Tokyo, Japan) were prospectively included. The CADe system was turned on only at withdrawal, and its output was displayed on secondary monitor. To study feasibility, inspection time, polyp detection rate (PDR), adenoma detection rate (ADR), sessile serrated lesion (SSL) detection rate (SDR), and the number of false positives were recorded. To study safety, (severe) adverse events ((S)AEs) were collected. Additionally, user friendliness was rated from 1 (worst) to 10 (best) by endoscopists. Results Mean inspection time was 10.8 +/- 4.3 min, while PDR was 55.6%, ADR 28.9%, and SDR 11.1%. The CADe system users estimated that < 20 false positives occurred in 81 colonoscopy procedures (90%). No (S)AEs related to the CADe system were observed during the 30-day follow-up period. User friendliness was rated as good, with a median score of 8/10. Conclusion Colonoscopy with this novel CADe system in a real-time setting was feasible and safe. Although PDR and SDR were high compared to previous studies with other CADe systems, future randomized controlled trials are needed to confirm these detection rates. The high SDR is of particular interest since interval CRC has been suggested to develop frequently through the serrated neoplasia pathway.
CRIS-Team WoS Importer:2022-10-07

Retrograde inspection vs standard forward view for the detection of colorectal adenomas during colonoscopy: A back-to-back randomized clinical trial - Rath, Timo; Pfeifer, Lukas; Neufert, Clemens; Kremer, Andreas; Leppkes, Moritz; Hoffman, Arthur; Neurath, Markus; Zopf, Steffen (World Journal of Gastroenterology, 2020)
BACKGROUND: The adenoma detection rate (ADR) is inversely associated with the incidence of interval colorectal cancer and serves as a benchmark quality criterion during screening colonoscopy. However, adenoma miss rates reach up to 26% and studies have shown that a second inspection of the right colon in retroflected view (RFV) can increase ADR. AIM: To assess whether inspection of the whole colon in RFV compared to standard forward view (SFV) can increase ADR. METHODS: Patients presenting for screening or surveillance colonoscopy were invited to participate in this randomized controlled trial and randomized into two arms. In RFV arm colonoscopy was initially performed with SFV, followed by a second inspection of the whole colon in RFV. In the SFV arm first withdrawal was performed with SFV, followed by a second inspection of the whole colon again with SFV. Number, size and morphology of polyps found during first and second inspection in each colonic segment were recorded and all polyps were removed and sent for histopathology in separate containers. RESULTS: Two hundred and five patients were randomly assigned to the RFV (n = 101) and SFV (n = 104) arm. In the RFV arm, both polyp detection rate (PDR) and ADR were increased under second inspection in RFV (PDR 1st SFV: 39.8%, PDR 2nd RFV: 46.6%; ADR 1st SFV: 35.2%, ADR 2nd RFV: 42%). Likewise, in the SFV arm, PDR and ADR were increased under second inspection (PDR 1st SFV: 37.5%, PDR 2nd SFV: 46.6%; ADR 1st SFV: 34.1%, ADR 2nd SFV: 44.3%) with no significant differences in ADR and PDR between the SFV and RFV arm. Mean number of adenomas per patient (APP) was increased in the RFV and SFV (APP RFV arm: 1st SFV: 1.71; 2nd RFV: 2.38; APP SFV arm: 1st SFV: 1.83, 2nd SFV:2.2). The majority of adenomas additionally found during second inspection in RFV or in SFV were located in the transverse and left-sided colon and were > 5 mm in size. CONCLUSION: Second inspection of the whole colon leads to increased adenoma detection with no differences between SFV and RFV. Hence, increased detection is most likely a feature of the second inspection itself but not of the inspection mode.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Adenoma; Adenoma detection rate; Colonoscopy; Colorectal cancer

Reverse switching from the biosimilar SB2 to the originator infliximab in previously switched patients with inflammatory bowel diseases: results of a prospective long-term cohort study - Fischer, Sarah; Donhauser, Moritz; Cohnen, Sarah Ellen; Fietkau, Konstantin; Vetter, Marcel; Grübel-Liehr, Maria; Dietrich, Peter; Rath, Timo; Wilfer, Angelika; Sologub, Ludmilla; Krebs, Sabine; Dörje, Frank; et al. (Therapeutic Advances in Gastroenterology, 2024)
A clinical study investigating the interchangeability between infliximab, a previously patented biotechnological produced drug (biological) and its successor product biosimilar SB2, which is highly similar to the existing reference product, in the treatment of patients with inflammatory bowel diseases Why was the study done? Biological drugs (like infliximab) are produced using various methods under the involvement of biotechnology. In contrary to generic drugs, due to their complex structure, biosimilars are not exactly the same molecule as the original substance. After the introduction of biosimilars, which are mostly less expensive than the original product, concerns were raised regarding the interchangeability of these substances. This study was conducted to investigate potential changes in efficacy and safety after multiple, so called switches (from the original product to its biosimilar and back). What did the researchers do? The research team switched a group of 95 patients diagnosed with inflammatory bowel disease and therefore treated with the original biologic drug infliximab to the biosimilar SB2, reverse switched them back to the original drug after 96 weeks and observed the patients for another 48 weeks. During the observational phase the disease activity, drug levels and potential side effects were monitored. What did the researchers find? The initial and the reverse switch had no relevant impact on the course of disease and additionally no safety issues occurred. During the 48 weeks observational period, 14.7% of patients discontinued therapy, which was not out of the expected range. Most potential side effects were not considered to be therapy-associated and only 4 of 95 patients discontinued treatment due to safety concerns. The drug levels remained stable during the switches. What do the findings mean? In this study, the research team found no impact of multiple switches on the disease activity in inflammatory bowel disease patients and moreover no safety issues. These findings support the practice of switching between the biologic originator substance infliximab and its biosimilar

Successful cyclosporin and ustekinumab combination therapy in a patient with severe steroid-refractory ulcerative colitis - Ganzleben, Ingo; Geppert, Carol-Immanuel; Osaba, Lourdes; Hirschmann, Simon; Nägel, Andreas; Glück, Christian; Hoffman, Arthur; Rath, Timo; Nagore, Daniel; Neurath, Markus; Atreya, Raja (Therapeutic Advances in Gastroenterology, 2020)
The therapeutic management of patients with severe steroid-refractory ulcerative colitis still represents a critical clinical challenge. In this setting, cyclosporin is an effective and rapidly acting induction treatment that is applied in combination with maintenance therapeutic agents like thiopurines or vedolizumab. Here, we present the case of a 33-year-old ulcerative colitis patient with severe steroid-refractory ulcerative colitis who refused surgical intervention and previously demonstrated no long-term benefit to anti-TNF antibody, vedolizumab, cyclosporin, thiopurines or tofacitinib treatment. Intravenous cyclosporin therapy was re-initiated in the patient and, after signs of clinical response, therapy with ustekinumab was additionally applied. After 11 weeks of well tolerated cyclosporin and ustekinumab combination therapy, cyclosporin was discontinued upon clinical and endoscopic remission. Subsequently, ustekinumab treatment has been effective in maintaining remission during the follow-up period of 195 days.
CRIS-Team Scopus Importer:2020-10-23
Keywords: cyclosporin; trough levels; ulcerative colitis; ustekinumab

Successful Long-term Treatment of Diversion Colitis with Topical Coconut Oil Application - Zundler, Sebastian; Dietz, Lisa; Matzel, Klaus E.; Geppert, Carol-Immanuel; Becker, Emily; Rath, Timo; Neurath, Markus; Atreya, Raja (American Journal of Gastroenterology, 2018)
CRIS-Team WoS Importer:2019-02-22

Targeting mucosal healing in Crohn’s disease: what the clinician needs to know - Klenske, Entcho; Bojarski, Christian; Waldner, Maximilian; Rath, Timo; Neurath, Markus; Atreya, Raja (Therapeutic Advances in Gastroenterology, 2019)
In recent years, mucosal healing has emerged as a key therapeutic goal in the clinical management of patients with Crohn’s disease, as it has been associated with improved long-term clinical outcomes. With the vast improvements in endoscopic imaging techniques and the increase in available treatment options, which reportedly are able to induce mucosal healing, the practising physician is left to wonder: how is endoscopic mucosal healing exactly defined in Crohn’s disease, and how can it effectively be achieved and monitored in daily clinical practice? Within this review, we will give an overview of the ongoing debate about the definition of mucosal healing and the modalities to monitor inflammation, and finally present available therapies with the capacity to induce mucosal healing.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Crohn’s disease; endoscopy; imaging; mucosal healing

Targeting of the Tec Kinase ITK Drives Resolution of T Cell–Mediated Colitis and Emerges as Potential Therapeutic Option in Ulcerative Colitis - Lechner-Grimm, Kristina; Mott, Stefanie; Al-Saifi, Ragheed; Knipfer, Lisa; Wirtz, Stefan; Atreya, Raja; Vieth, Michael; Rath, Timo; Fraass, Tina; Winter, Zoltan; August, Avery; Luban, Jeremy; et al. (Gastroenterology, 2021)
Background & Aims: The molecular checkpoints driving T cell activation and cytokine responses in ulcerative colitis (UC) are incompletely understood. Here, we studied the Tec kinase ITK in UC. Methods: We analyzed patients with inflammatory bowel disease (n = 223) and evaluated ITK activity as well as the functional effects of cyclosporine-A (CsA). In addition, 3 independent murine colitis models were used to investigate the functional role of ITK. Finally, the activity of ITK was blocked via pharmacological inhibitors and genetically engineered mice. Readout parameters were mini-endoscopy, histopathology, mucosal T cell apoptosis, and cytokine production. Results: We found an expansion of pITK-expressing mucosal CD4+ T cells in UC rather than Crohn's disease that correlated with disease severity. CsA suppressed activation of ITK in cultured CD4+ T cells and calcineurin-containing microclusters adjacent to the T cell receptor signaling complex. Functionally, the capacity of CsA to suppress activity of experimental colitis was critically dependent on ITK. Genetic inactivation of Itk via gene targeting or induction of allele-sensitive Itk mutants prevented experimental colitis in 3 colitis models, and treatment with pharmacological ITK blockers suppressed established colitis. In addition, ITK controlled apoptosis and activation of mucosal Th2 and Th17 lymphocytes via NFATc2 signaling pathways. Conclusions: ITK activation was detected in UC and could be down-regulated in cultured T cells by CsA administration. Selective targeting of ITK emerges as an attractive approach for treatment of chronic intestinal inflammation and potentially UC by driving resolution of mucosal inflammation.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Cyclosporine A; Cytokines; IBD; ITK; Therapeutic Strategies

Technical success, resection status, and procedural complication rate of colonoscopic full-wall resection: a pooled analysis from 7 hospitals of different care levels - Krutzenbichler, Irmengard; Dollhopf, Markus; Diepolder, Helmut; Eigler, Andreas; Fuchs, Martin; Herrmann, Simon; Kleber, Gerhard; Lewerenz, Bjoern; Kaiser, Christoph; Lilje, Tilman; Rath, Timo; Agha, Ayman; et al. (Surgical Endoscopy, 2020)
Introduction: Endoscopic full-thickness resection (eFTR) using the full-thickness resection device (FTRD®) is a novel minimally invasive procedure that allows the resection of various lesions in the gastrointestinal tract including the colorectum. Real-world data outside of published studies are limited. The aim of this study was a detailed analysis of the outcomes of colonoscopic eFTR in different hospitals from different care levels in correlation with the number of endoscopists performing eFTR. Material and methods: In this case series, the data of all patients who underwent eFTR between November 2014 and June 2019 (performed by a total of 22 endoscopists) in 7 hospitals were analyzed retrospectively regarding rates of technical success, R0 resection, and procedure-related complications. Results: Colonoscopic eFTR was performed in 229 patients (64.6% men; average age 69.3 ± 10.3 years) mainly on the basis of the following indication: 69.9% difficult adenomas, 21.0% gastrointestinal adenocarcinomas, and 7.9% subepithelial tumors. The average size of the lesions was 16.3 mm. Technical success rate of eFTR was achieved in 83.8% (binominal confidence interval 78.4–88.4%). Overall, histologically complete resection (R0) was achieved in 77.2% (CI 69.8–83.6%) while histologically proven full-wall excidate was confirmed in 90.0% (CI 85.1–93.7%). Of the resectates obtained (n = 210), 190 were resected en bloc (90.5%). We did not observe a clear improvement of technical success and R0 resection rate over time by the performing endoscopists. Altogether, procedure-related complications were observed in 17.5% (mostly moderate) including 2 cases of acute gangrenous appendicitis requiring operation. Discussion: In this pooled analysis, eFTR represents a feasible, effective, and safe minimally invasive endoscopic technique.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Endoscopic full-thickness resection (eFTR); Endoscopic resection; Full-thickness resection device (FTRD®); Polypectomy; ‘WALL RESECT’

THE FIRST REAL-LIFE MULTICENTRE, INTERNATIONAL, PROSPECTIVE VALIDATION STUDY OF THE ELECTRONIC CHROMOENDOSCOPY SCORING SYSTEM (PICASSO-THE PADDINGTON INTERNATIONAL VIRTUAL CHROMOENDOSCOPY SCORE) AND ITS OUTCOME IN ULCERATIVE COLITIS PATIENTS - Iacucci, Marietta; Smith, Samuel C.; Bazarova, Alina; Shivaji, Uday N.; Bhandari, Pradeep; Cannatelli, Rosanna; Daperno, Marco; Ferraz, Jose G.; Goetz, Martin; Gui, Sean X.; Hayee, Bu; De Hertogh, Gert; et al. (GASTROINTESTINAL ENDOSCOPY, 2020)
CRIS-Team WoS Importer:2021-02-19

The first real-life multicentre prospective validation study of the electronic chromoendoscopy score (Paddington International Virtual ChromoendoScopy ScOre) and its outcome in ulcerative colitis - Iacucci, M.; Smith, S. C.; Bazarova, A.; Shivaji, U. N.; Bhandari, P.; Cannatelli, R.; Daperno, M.; Ferraz, J. G.; Goetz, M.; Gui, X.; Hayee, B.; De Hertogh, G.; et al. (JOURNAL OF CROHNS & COLITIS, 2020)
CRIS-Team WoS Importer:2020-04-10

The first virtual chromoendoscopy artificial intelligence system to detect endoscopic and histologic remission in Ulcerative Colitis - Iacucci, M.; Cannatelli, R.; Parigi, T. L.; Buda, A.; Labarile, N.; Nardone, O. M.; Tontini, G. E.; Rimondi, A.; Bazarova, A.; Bhandari, P.; Bisschops, R.; De Hertogh, G.; et al. (JOURNAL OF CROHNS & COLITIS, 2022)
CRIS-Team WoS Importer:2022-05-13

The JAK1/3 Inhibitor to Tofacitinib Suppresses T Cell Homing and Activation in Chronic Intestinal Inflammation - Gerlach, Katharina; Lechner, Kristina; Popp, Vanessa; Offensperger, Laura; Zundler, Sebastian; Wiendl, Maximilian; Becker, Emily; Atreya, Raja; Rath, Timo; Neurath, Markus; Weigmann, Benno (Journal of Crohns & Colitis, 2021)
Background and Aims: The molecular mechanism of action of the Janus kinase [JAK] inhibitor tofacitinib is poorly understood. Methods: Here we analysed the inhibitory effect of tofacitinib on mucosal and blood T cells from patients with ulcerative colitis [UC]. Furthermore, tofacitinib treatment was analysed in experimental colitis models and wound healing. Additionally, tofacitinib effects were analysed in bioassays. Results: Tofacitinib significantly reduced T cell-derived inflammatory cytokine production [Th2, Th9, Th17] in patients with active UC. Additionally, impaired expression of the homing receptors alpha4/beta1 and alpha4/beta7, as well as reduced gut homing capacity of T cells in a humanised mouse model of colitis, were observed. Tofacitinib suppressed acute and chronic oxazolone colitis, compared with untreated wild-type mice, associated with downregulation of cytokines produced by Th2, Th9, and Th17 cells. Functionally, tofacitinib induced apoptosis of intestinal epithelial cells and prevented mucosal wound healing in vivo at higher concentration. Thus, our findings suggest that tofacitinib is quite effective in protecting from colitis, by inhibition of a bundle of T cell-derived cytokines like IL-5, IL-6, IL-9, IL-13, and IL-17A. Conclusions: Application of tofacitinib emerges as an attractive concept for treatment of chronic intestinal inflammation at lower concentrations, whereas higher concentrations require attention due to prolonged wound healing.
CRIS-Team Scopus Importer:2021-05-07
Keywords: cytokines; inflammatory bowel disease; T cells; Tofacitinib; wound healing

The Ominous Ouzo Party - A Case Series of Four Patients with Accidental Alkali Ingestion - Vetter, Marcel; Rath, Timo; Siebler, Jürgen; Waldner, Maximilian; Neurath, Markus; Pfeifer, Lukas (Clinical and Experimental Gastroenterology, 2021)
Background: Ingestion of alkaline fluids is a common problem, which can lead to perforations, strictures and malignancy. We present a rare case series of several patients who accidentally ingested the same alkaline substance in different doses.
CRIS-Team WoS Importer:2021-07-30

The outcome of patients with inflammatory bowel disease-associated colorectal cancer is not worse than that of patients with sporadic colorectal cancer-a matched-pair analysis of survival - Vitali, Francesco; Wein, Axel; Rath, Timo; Eckstein, Markus; Neufert, Clemens; Siebler, Jürgen; Atreya, Raja; Hartmann, Arndt; Hohenberger, Werner; Weber, Klaus; Neurath, Markus; Grützmann, Robert; et al. (International Journal of Colorectal Disease, 2021)
Purpose Patients with inflammatory bowel disease (IBD) have an increased risk for colorectal cancer (CRC). In IBD patients, cancer is often diagnosed in advanced stages and conflicting data on survival compared to sporadic CRC have been reported. The aim of this study was to directly compare clinical characteristics and prognosis of patients with IBD-CRC and sporadic CRC. Methods The clinical and pathological data of 63 patients with IBD-CRC and 3710 patients with sporadic CRC treated at the University Hospital of Erlangen between 1995 and 2015 were compared. Forty-seven M0 patients with IBD were matched with sporadic CRC patients after curative resection (R0) according to tumor localization, stage, sex, and year of treatment. Overall and disease-free survival were compared. Results Sixty-three patients presented IBD-CRC. Fifty were affected with ulcerative colitis (UC) and 13 with Crohn's disease (CD). CRC was diagnosed within 1.45 years since last endoscopic surveillance. Twelve patients (19%) had a diagnosis of primary sclerosing cholangitis. In matched analysis, IBD patients were diagnosed with CRC at younger age compared to sporadic CRC and were more likely to have right-sided CRC (40% versus 23.3%) and rare histological subtypes (19% versus 9.2%). No differences in 5-year overall (78.7 versus 80.9 months) and 5-year disease-free survival (74.5 versus 70.2 months) were noted. Conclusion IBD-CRC patients were younger and more frequently had right-sided carcinomas compared to sporadic CRC. CRC in IBD patients did not show survival difference compared to matched-pair sporadic CRC patients without distant metastases after curative resection. Surveillance might be important for early detection of CRC in IBD patients.
CRIS-Team WoS Importer:2021-12-17

The TLR9 agonist cobitolimod induces IL10 producing wound healing macrophages and regulatory T cells in ulcerative colitis - Schmitt, Heike; Ulmschneider, Julia; Billmeier, Ulrike; Scarozza, Patrizio; Sonnewald, Sophia; Reid, Stephen; Atreya, Imke; Rath, Timo; Zundler, Sebastian; Langheinrich, Melanie; Schüttler, Jürgen; Hartmann, Arndt; et al. (Journal of Crohns & Colitis, 2020)
BACKGROUND AND AIMS: The topically applied Toll-like receptor 9 (TLR9) agonist cobitolimod is a first-in-class DNA-based oligonucleotide that demonstrated therapeutic efficacy in clinical trials with ulcerative colitis (UC) patients. We here characterized its anti-inflammatory mechanism in UC. METHODS: Luminal cobitolimod administration was evaluated in an experimental DSS-induced colitis model. Cultured blood and mucosal cells from UC patients were treated with cobitolimod and analyzed via microarray, qRT-PCR, ELISA and flow cytometry. Intestinal slides of cobitolimod treated UC patients were analyzed by immunohistochemistry. RESULTS: Cobitolimod administration markedly suppressed experimental colitis activity and microarrays analyses demonstrated mucosal IL10 upregulation and suppression of IL17 signaling pathways. Cobitolimod treatment was associated with significant induction of mucosal IL10+ Tr1 and Treg cells and suppression of Th17 cells. TLR9 knockout mice indicated that cobitolimod requires TLR9 signaling for IL10 induction. In UC patients, mucosal TLR9 levels correlated with severity of inflammation. Cobitolimod inhibited IL17A and IL17F, but increased IL10 and FoxP3 expression in cultured intestinal UC T cells. Cobitolimod-mediated suppression of intestinal IL17+ T cells was abrogated by IL10 blockade. Furthermore, cobitolimod led to heightened IL10 production by wound healing macrophages. Immunohistochemistry in intestinal biopsies of cobitolimod treated UC patients indicated increased presence of IL10+ mononuclear and regulatory T cells, as well as reduction of IL17+ cells. CONCLUSION: Our studies suggest that activation of TLR9 via cobitolimod might represent a novel therapeutic approach in UC, as it suppresses Th17 cells and induces anti-inflammatory IL10+ macrophages and regulatory T cells, thereby modifying the dysregulated intestinal cytokine balance.
EVALuna2:212910
Keywords: Ulcerative colitis; TLR9; cobitolimod

Use of Fluorescent Dyes in Endoscopy and Diagnostic Investigation - Hoffman, Arthur; Atreya, Raja; Rath, Timo; Neurath, Markus (Visceral Medicine, 2020)
Background: The advancement of innovative endoscopic technology in terms of improving the visualization of the mucosa has been of significant benefit. Summary: Advancements in image resolution, software processing, and optical filter technology have resulted in several techniques complemental to traditional white light endoscopy. These new techniques provide a real-time optical diagnosis as well as virtual histology of detected lesions. Optical molecular imaging permits a functional assessment within cells. Key Message: Optical molecular imaging provides an understanding of cellular processes and permits validation of the specificity of fluorescent tracers and the possibility of quantifying the signal.
CRIS-Team Scopus Importer:2020-04-07

Validation of the 'Inflammatory Bowel Disease-Distribution, Chronicity, Activity [IBD-DCA] Score' for Ulcerative Colitis and Crohn ' s Disease - Lang-Schwarz, Corinna; Angeloni, Miriam; Agaimy, Abbas; Atreya, Raja; Becker, Christoph; Dregelies, Theresa; Danese, Silvio; Flejou, Jean-Francois; Gassler, Nikolaus; Grabsch, Heike; Hartmann, Arndt; Kamaradova, Katerina; et al. (Journal of Crohns & Colitis, 2021)
Background and Aims: Histological scoring plays a key role in the assessment of disease activity in ulcerative colitis [UC] and is also important in Crohns disease [CD]. Currently, there is no common scoring available for UC and CD. We aimed to validate the Inflammatory Bowel Disease [IBD]-Distribution [D], Chronicity [C], Activity [A] score [IBD-DCA score] for histological disease activity assessment in IBD.
CRIS-Team WoS Importer:2021-11-12